Unveiling the hidden culprit: salinity inhibition on phosphorus recovery from high-salt wastewater via vivianite crystallization - Yi Cai; Yifan Du; Pin Zhao; Weilong Song; Xinhua Wang (Water Research, 2026)

Seismic characteristics, distribution and origin of shallow gas on the continental shelf offshore the Pearl River Estuary, northern South China Sea - Jian Li; Wei Li; Tiago M. Alves; Yingci Feng; Jie Sun; Yantao Yao; Jiaxian Huang; Pin Wang; Qinqin Tang; Wenhuan Zhan (Marine Geology, 2026)

Expression, prognostic value and function of LMBR1L in gastric cancer - Song Liang; Chaosheng Zhang; Chuanjun Wang; Yongkang Liang; Xueyi Feng; Chuansi Wang; Pin Jiang; Shenwei Wu; Xiuming Lu (Molecular Genetics and Genomics, 2026)

Rainstorm‑driven highly chlorine‑reactive DOM increases disinfection byproduct risks in drinking water - Zhengdi Wu; Pin Wang; Yu Lei; Yayun Zhang; Zhimin Qiang; Wenhai Chu (Water Research, 2026)

Predictive model of perchlorate adsorption by imidazole-N modified activated carbon: Experimental validation and mechanistic analysis - Xinyu Sun; Jianhui Guo; Jianbing Wang; Jiushuai Deng; Cesar Niedo-Delgado; Chunrong Wang; Pin Hou (Journal of Water Process Engineering, 2026)

Constrained stochastic data sampling for deep learning–based time-lapse hydraulic tomography under reactive-induced permeability evolution - Zi-Yan Chou; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang; Ying-Fan Lin; Tian-Chyi Jim Yeh (Journal of Hydrology, 2026)

Classification of hemocyte subpopulations in the clam Meretrix Petechialis and their differential immune-associated responses to Vibrio infection - Jing Tian; Hongxia Wang; Pin Huan; Baozhong Liu (Fish & Shellfish Immunology, 2026)

Interfacial electron redistribution and tandem active sites enable enhanced nitrate to ammonia conversion in Zr-MOF/MoS2 heterostructures - Naveen Karuppusamy; Zi-Yan Zhan; Ruspika Sundaresan; Chun Hsien Wu; Pandiyarajan Anand; Jeyakumar Karthikeyan; Hsu-Feng Lee; Hung-Pin Hsu; Yu-Cheng Shao; Yi-Ping Wang; Ching-Wei Tung (Chemical Engineering Journal, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Spatially distributed modeling of biofilm-induced hydrodynamic evolution in porous media - Hongcheng Zhang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Wang Kai Tong; Jia Jie Zou; Min-tian Gao; Zhi Li; Xihua Wang; Yalei Zhang; Kah Hon Leong; Swee Pin Yeap; et al. (Journal of Hydrology, 2026)

Towards standardized molecular monitoring of HABs: A consensus guide to qPCR - Uwe John; Dave Clarke; Holly Bowers; Shauna Murray; Antonella Penna; Amna Ashfaq; Karl Blyth Andree; Mathiroopini Andipalagan; Elisa Berdalet; Silvia Casabianca; Catarina Churro; Anette Engesmo; et al. (Harmful Algae, 2026)

Global gap-free aerosol optical depth reconstruction based on the fusion of satellite and reanalysis data - Zheng Wang; Wencai Zhang; Tingting Xie; Yuxin Wang; Min Qiao; Tseng Chun-Pin; Xiaoxian Chen; Tianhao Gong (Advances in Space Research, 2026)

Draw solution contamination undermines FO-MD stability for transfer station leachate treatment - Weilong Song; Mindi He; Yifei Xie; Boyan Xu; Pin Zhao; Xinhua Wang; Ng Yong (Water Research, 2026)

Synergistic microbubble ozonation and CaO2 activation for refinery sludge valorization: Organic carbon liberation and petroleum hydrocarbon degradation - Di Shu; Ziyang Lou; Kaiyan Yang; Zhiyi Sun; Hui Wang; Zhaowen Cheng; Pin Zhou; Shuping Zhang; Nanwen Zhu; Luochun Wang (Journal of Environmental Management, 2026)

Effects of dietary rumen-protected bile acids on muscle fiber composition and drip loss in Hu sheep (Ovis aries): insights from transcriptomic and metabolomic analyses - Zhe Wang; Manman Hou; Dan Hu; Jie Huang; Qi Liu; Pin Song; Yue Chen; Pengnan Chen; Yuyang Yin; Aizhi Cao; Yufeng Li; Yingdong Ni (Food Bioscience, 2026)

The dynamics of microbial communities in the host, water and sediment during the metamorphosis of Ruditapes philippinarum larvae - Yong Huang; Hongxia Wang; Jun Fang; Pin Huan; Baozhong Liu (Aquaculture, 2026)

Toward sustainable utilization of high-iron red mud: A novel calcification-biomassification process for iron enrichment and magnetic recovery - Xingjian Wang; Yiyong Wang; Tingan Zhang; Zhiyu Fan; Zhe Ning; Pin Shao; Jidong Li (Process Safety and Environmental Protection, 2026)

Genome-wide identification, expression analysis and antiviral function of RIG-I-like receptors (RLRs) in basal chordate Branchiostoma japonicum - Yueying Du; Yuhang Deng; Ruixue Liu; Jialing Yuan; Yunxia Wang; Su Wang; Pin Nie; Xiaojun Song (Fish & Shellfish Immunology, 2026)

Numerical analysis of the interaction mechanism between the dual-row jet hydraulic mining collector and deep-sea sediment - Pin-Jian Wang; Li Li; Jia-Bin Wu (Computers and Geotechnics, 2026)

Aging attenuates threat: how moderate aging of microplastics suppresses antibiotic resistance gene proliferation during sludge anaerobic digestion - Jinling He; Ai Zhang; Lin Wang; Qian Ping; Pin Gao; Yanan Liu (Bioresource Technology, 2026)

Microbiological spectrum, clinical outcomes, and risk factors for bloodstream infections during immune checkpoint inhibitor therapy: a nested case-control study - Deng Pan; Huan Wang; Yu Fang; Jun Lu; Wendi Zhang; Pin Peng; Minghao Fang (Infectious Diseases, 2026)

Occurrence, distribution, and risk assessment of antibiotics in typical aquaculture environment of Southern Jiangsu, China - Zhen Kuang; Wenfeng Zheng; Weilong Song; Pin Zhao; Xinhua Wang (Journal of Environmental Sciences, 2026)

Simultaneous removal of fluoride and disinfection by-product precursors through Zr salt enhanced coagulation - Zhanghan Li; Pin Wang; Cheng Ye; Jiacheng Luo; Yayun Zhang; Wenhai Chu (Journal of Environmental Sciences, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Heteroatom bridging chemistries enabling fast polysulfide redox and stable lithium deposition - Guangfeng Zeng; Ruiqing Luo; Yumei Qin; Xue Li; Fangting Xie; Jiajia Wang; Shulong Wang; Jingru Liang; Zhiqi Ma; Duming Wei; Qi-Pin Qin; Xiang-Long Huang (Chemical Engineering Journal, 2026)

Design Rules for Robust Coronary Artery Segmentation: A Systematic Analysis of Dataset Size, Windowing, Architectures, and Vessel Geometry - Ming-Hui Hung; Yu-Wei Chiang; Hao-Yun Liu; Han-Hsuan Chu; Yu-Sen Huang; Pin-Yi Chiang; Hsin-Ming Chen; Tzung-Dau Wang; Shyh-Jye Chen; Wen-Jeng Lee (Annals of Biomedical Engineering, 2026)

SAR-to-EO image translation with multi-kernel-size convolutions - Jingqin Mu; Yuzhu Wang; Sheng Zhan; Guoqing Yao; Jiarui Tian; Pin Liu (International Journal of Remote Sensing, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Joint inversion of hydraulic and thermal parameter fields using a CNN-based framework and transient hydraulic tomography - Che-Wei Liang; Jui-Pin Tsai; Zi-Yan Chou; Chia-Hao Chang; Bo-Tsen Wang (Journal of Hydrology, 2026)

Treating waste with waste: Efficient recovery of sodium, aluminum, and iron from high-iron red mud by Calcification-Biomassification process - Xingjian Wang; Yiyong Wang; Tingan Zhang; Zhiyu Fan; Zhe Ning; Pin Shao; Jidong Li (Journal of Environmental Chemical Engineering, 2026)

Diversified rotation reduced N2O emissions by shaping N-cycling microbial communities and increasing their network complexity - Taobing Yu; Lang Cheng; Pin Wang; Lei Yang; Tengxiang Lian; Huadong Zang; Zhaohai Zeng; Yadong Yang (Journal of Environmental Sciences, 2026)

Sea buckthorn for future foods: bioactive mechanisms, synthetic biology, and precision delivery systems - Nan Li; Peidong Fan; Lulu Wang; Luole Feng; Hui Long; Wenjuan Yang; Jing Wang; Yanni Zhao; Huan Liu; Yuxi Guo; Pin Gong (Food Research International, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Immunomodulatory mechanism of Pleurotus eryngii polysaccharides in acrylamide-induced mice via the P2X7-NLRP3 pathway, metabolic homeostasis and gut microbiota - Jing Wang; Xiuxiu Liu; Dongliang Jin; Man Wang; Nan Zhang; Yanni Zhao; Wenjuan Yang; Nan Li; Xuefeng Chen; Pin Gong (Food Bioscience, 2026)

Recent advances in biochar-based composite phase change materials - Pin Jin Ong; Reuben J. Yeo; Anqi Sng; Suxi Wang; Warintorn Thitsartarn; FuKe Wang; Junhua Kong; Rong Ji; Beng Hoon Tan; Dan Kai; Pei Wang; Jianwei Xu; et al. (Biomass and Bioenergy, 2026)

Intestinal organoids as advanced modeling platform for food research: a review - Xu Wang; Yanqiu Xia; Jin Wang; Yan Zhang; Pin Lv; Yi Wang (Critical Reviews in Food Science and Nutrition, 2026)

Applying semi-supervised learning algorithms in real-environment solid waste classification - Dong–Ying Lan; Pin–Jing He; Hui–Huang Zou; Rong–Rong Kan; Yi Wang; Fan Lü; Hua Zhang (Resources, Conservation and Recycling, 2026)

Widely targeted metabolomics reveals chemical mechanism of bloating in Rosa roxburghii Tratt juice induced by vitamin C and its chiral isomers - Hong Yang; Yuting Liu; Xinying Wang; Wenxin Zhang; Bo Peng; Dalong Chen; Angze Gao; Weixin Huang; Pin Qian; Deshun Yu; Yifu Tian; Xianzhi Dong (Food Chemistry, 2026)

High ambient temperature during pregnancy and offspring cerebral palsy: A population-based case-control study in California - Haoran Zhuo; Joshua L. Warren; Giselle Bellia; Pin Wang; Kai Chen; Zeyan Liew; Tormod Rogne (Environmental Research, 2026)

Ophiocordyceps Polyrhachicola (Hypocreales, Ophiocordycipitaceae), a New Species of Ant Associated Fungal Parasite in China - Jia‐Ping Wang; Chada Norphanphoun; Yu Yang; Yuan‐Pin Xiao; Kevin D. Hyde; Yong Wang (New Zealand Journal of Botany, 2026)
Ophiocordyceps , the largest genus within the family Ophiocordycipitaceae, is known for its parasitism on many insect hosts. Recent advances in global biodiversity research have enhanced the classification and ecological understanding of this genus, underscoring its pivotal role in global ecosystems. As the type genus of Ophiocordycipitaceae, Ophiocordyceps has undergone extensive taxonomic revision based on comprehensive studies. In this study, Ophiocordyceps polyrhachicola , a novel species from China that parasitizes the ants of the genus Polyrhachis inhabiting leaf litter of temperate deciduous forests is introduced. Species placement is supported corroborated by morphological observations and phylogenetic analyses of a multi‐locus dataset comprising ITS, LSU, SSU, rpb1 , rpb2 , and tef1‐α sequences. Detailed comparisons with closely related taxa reveal distinctive morphological traits and molecular characteristics, establishing O. polyrhachicola as a unique and well‐delimited species within the genus.

Botulinum neurotoxin A alleviates Deinagkistrodon acutus venom-induced limb injury through promoting macrophage polarization in rabbits - Lutao Xie; Haohao Wu; Linjie Lai; Wang Du; Jiefeng Xu; Pin Lan (Toxicon, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Long-term low-dose N, N-dimethylformamide exposure disturbs hepatic lipid and glucose homeostasis in mice - Shu-Jun Hong; Ming-Bao Zhang; Le-Yi Qi; Tian-Hao Zhao; Pin Wang; Tao Zeng (Toxicology, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

The radial distribution of temperature and electrical conductivity in lightning core current-carrying channel and its time evolution - Pin Lyu; Ping Yuan; Wangsheng Wang; Yingying An; Tingting An; Hong Deng; Lizhen Yuan (Atmospheric Research, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Molecular weight: A key factor influencing the removal efficiency of dissolved organic matter and disinfection byproducts by an aquatic plant - Ruixin Qu; Shunke Ding; Yingying Zhou; Zhenqi Du; Pin Wang; Michael R. Templeton; Wenhai Chu (Water Research, 2025)

Emerging heterocyclic nitrogenous disinfection byproducts: Occurrence, precursors, and mechanisms of halogenated pyridines - Pin Wang; Bei Ye; Youhei Nomura; Taku Fujiwara (Journal of Environmental Chemical Engineering, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

Marine quorum quenching consortium for biofouling control in membrane bioreactor under salinity stress - Weilong Song; Chengyu Wan; Ziang Ding; Boyan Xu; Pin Zhao; Xinhua Wang; How Yong Ng (Water Research, 2025)

Structural and mechanistic insights into halogenated disinfection byproducts of tannic acid with toxicity analysis during chloramination - Shu-Xi Guo; Hui-Xian Hu; Pin Wang; Yu-En Guo; Yao Lu; Ye Du (Water Research, 2025)

Seismic evidence for magmatism-driven mud volcanism in the northern continental margin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Marine and Petroleum Geology, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Microplastics provide new niches for nitrifiers to maintain nitrification performance in nitrifying bioreactors - Peikun Yuan; Yang Wang; Yipeng Lu; Zheng Wei; Pin Gao (Environmental Research, 2025)

Lactate to caproate chain elongation: Kinetic characterization and theoretical model for real-time monitoring - Yujie Wang; Junjie Qiu; Fan Lü; Hua Zhang; Pin-Jing He (Chemical Engineering Journal, 2025)

Three-dimensional material point analysis of the Guanghua landslide influenced by topographic constraints - Yi-Pin Peng; Kuo-Hsin Yang; Wei-Lin Lee; Tatag Yufitra Rus; Shih-Hao Cheng; Jyun-Yen Wang; Chihping Kuo (Landslides, 2025)

Exploring the mechanism of cinobufagin on gastric cancer based on proteomics, molecular dynamics, in vitro and in vivo experiment - Pin Wang; Xia Zhang; Hanwei Ma; Youcheng Zhang (Toxicology and Applied Pharmacology, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Identification, occurrence, and toxicity prediction of alkylphenolic disinfection by-products in disinfected combined sewer overflows - Yayun Zhang; Pin Wang; Rong Xiao; Wenyuan Yang; Fang Yuan Jiang; Wen Hai Chu (Journal of Hazardous Materials, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Freshwater microalgae-mediated engineered nanoparticles: Sustainable approach for heavy metals remediation - Manish Sutradhar; Raju Kumar Sharma; Gobinda Dey; Uttara Sukul; Koyeli Das; Md. Taharia; Pin-Yun Lin; Shafiqa Ali; Chin-Wen Wang; Chien-Yen Chen (Bioresource Technology, 2025)

Risk Perception and Adaptations to Flood Disaster in Coastal Tainan, Taiwan - Hsiao‐Wen Wang; Pin‐Han Kuo; Jie‐Wun Yu (Irrigation and Drainage, 2025)
The southwest coast of Taiwan is vulnerable to flooding. This study investigated flood risk perception and adaptive behaviour among residents of five coastal villages in coastal Tainan City, Taiwan, through a questionnaire survey yielding 97 valid responses. Descriptive and inferential statistics were employed to analyse demographic characteristics, disaster experience, risk perception and adaptive behaviour, and to examine differences across multiple variables. Results indicated the potential effectiveness of the flood‐resilient community programme in promoting adaptive behaviour, and highlighted the need for further in‐depth investigation to disentangle the factors influencing risk perception and adaptive behaviours. A significant positive relationship between understanding levels and the perceived helpfulness of preparedness information highlights the importance of effective information dissemination to enhance community resilience. Communication preferences have shifted toward mobile technologies for receiving timely warnings and preparedness information. Despite these findings, results indicated a persistent preference for engineering solutions and reliance on government infrastructure rather than personal preparedness. The study recommends a necessity for shared responsibility between the government and individuals, and emphasizes improving public risk perception related to flood preparedness and utilizing preferred communication channels to disseminate key information.

Towards sustainable construction: A cost-effective framework for bird monitoring from on-site collected videos leveraging deep active learning and synthetic training data - Hao Xu; Jun Kang Chow; Pin Siang Tan; Xin Mao; Kuan-fu Liu; Yu-Hsing Wang (Journal of Cleaner Production, 2025)

Variations in the leaf economics spectrum, anatomical, ultrastructural, and stomatal traits of five tree species in the urban-rural air pollution environment - Xiangru Yan; Pin Li; Xianjie Wu; Jiahui Wang; Zejin Wang; Jingliang Xu; Xiaofan Hou; Dayong Fan; Zhengbing Yan; Enzai Du (Journal of Environmental Sciences, 2025)

Genomic and phylogenetic analyses of the domoic acid biosynthesis genes in the benthic diatom Nitzschia navis-varingica (Bacillariophyceae) - Zongmei Cui; Hui Wang; Po Teen Lim; Suh Nih Tan; Yuichi Kotaki; Chui Pin Leaw; Nansheng Chen (Harmful Algae, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

In vitro starch digestion and release of polyphenols from corn starch-polyphenols complex - Shusheng Wang; Jianing Zhang; Jiayu Wang; Pin Lv; Shuo Tian; Yuchun Su (Food Bioscience, 2025)

Applications, life cycle assessment, and circular economy of bamboo torrefaction for sustainability: A state-of-the-art review - Wei-Hsin Chen; Pin-Chun Liang; Wei-Yi Wang; Pen-Chi Chiang; Jiří Ryšavý; Jakub Čespiva; Jo-Shu Chang (Bioresource Technology, 2025)

Hydraulic heterogeneity estimation with transient hydraulic tomography and convolutional encoder-decoder neural network - Yu-Kai Chen; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang (Stochastic Environmental Research and Risk Assessment, 2025)

The roles of reactive nitrogen species in chloramination of phenolic compounds: Insights into kinetics and by-product formation mechanisms - Pin Wang; Bei Ye; Youhei Nomura; Taku Fujiwara (Chemical Engineering Journal, 2025)

Spatial-temporal projections of population exposure to extreme heat in China under different emission and population scenarios - Chenghua Shen; Yue Sheng; Yao Li; Pin Wang (Natural Hazards, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Contributions of urbanization and population growth to changes in urban flood exposure in recent decades - Ziyi Tang; Pin Wang; Yao Li; Chaohui Chen; Yihan Lou; Tangao Hu (Sustainable Cities and Society, 2025)

Enhanced deep eutectic solvent extraction of phenolic compounds from hawthorn seeds with ultrasonic and resin in-situ adsorption assistance: Process optimization, component analysis, and extraction mechanism - Pengfei Jiao; Xingmei He; Zhihao Zhou; Xuan Wang; Yunrui Zhang; Pin Chang; Xin Zhang; Peng Wang; Pengpeng Yang; Qiuhong Niu (Food Chemistry, 2025)

Performance Analysis of Poppet Valves in Deep-Sea Hydraulic Systems: Considering Viscosity–Pressure Characteristics - Pin-Jian Wang; Jia-Bin Wu (Journal of Marine Science and Engineering, 2025)
Deep-sea hydraulic systems, powering a wide range of numerous deep-sea operating equipment, employ many poppet valves to adjust the pressure and flow rate, thereby realizing precise movements of the actuators. With greater depths and ambient pressures, the hydraulic oil viscosity increases exponentially, leading to a significant difference in the performance of the poppet valve compared to on-land usage and across varying depths. Based on the shear stress transport (SST) k-ω turbulence model and the dynamic mesh method, a computational fluid dynamics (CFD) model of the poppet valve was established. With the viscosity–pressure characteristics considered, the performance of the poppet valve was analyzed under different depths, different inlet flow rates, and different cracking pressures. The results indicate significant performance deterioration in poppet valves at increased depths, characterized by increased pressure loss and extended response rise time. At 11 km underwater, the pressure loss can be 7 MPa larger than the preset cracking pressure of 10 MPa, and the rise time is doubled compared with the land condition. It is recommended to use hydraulic oils with a lower initial viscosity and a slower increase in viscosity with pressure in deep sea conditions.

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Estimating basin-scale heterogeneous hydraulic diffusivity fields based on signal decomposition and river stage tomography - Bo-Tsen Wang; Yu-Li Wang; Chia-Hao Chang; Chin-Tsai Hsiao; Jordi Mahardika Puntu; Ping-Yu Chang; Jui-Pin Tsai (Journal of Hydrology, 2025)

Mechanistic elucidation of ultraviolet light and peracetic acid coupling-driven enhancements in short-chain fatty acid production from sludge: Reactive species-induced organic solubilization and microbial function regulation - Ai Zhang; Zhilin Shen; Yongqiang Ding; Nan Jiang; Xianbao Xu; Jinling He; Lin Wang; Pin Gao (Journal of Environmental Management, 2025)

One-step controllable synthesis of N-doped porous carbon derived from ZIF-8 for efficient capacitive deionization - Pin Hou; Jiaqi Yan; Xiaoyu Yang; Ridha Djellabi; Xinrui Ge; Xinyu Sun; Jianli Jia; Jianbing Wang (Journal of Environmental Chemical Engineering, 2025)

Recent advances in low-temperature phase change materials for cold chain logistics - Xiang Yun Debbie Soo; Pin Jin Ong; Yee Kiat Zachary Lim; Suxi Wang; Warintorn Thitsartarn; FuKe Wang; Junhua Kong; Rong Ji; Nikodem Tomczak; Beng Hoon Tan; Pei Wang; Jianwei Xu; et al. (International Journal of Refrigeration, 2025)

The mechanism of perilla oil in regulating lipid metabolism - Jiawei Xia; Yi Wang; Xin Li; Li Liu; Pin Zhang; Wendong Dai; Peng Luo; Guoze Wang; Yanhong Li (Food Chemistry, 2025)

Comparative analysis of phytochemical and antioxidant potential in traditional medicinal plants: Insights from solvent-based extractions - Shafiqa Ali; Haibat Ali; Ashiq Hussain; Gobinda Dey; Chin-Wen Wang; Md Taharia; Pin-Yun Lin; Raju Kumar Sharma; Ping-Gune Hsiao; Chien Yen Chen (Food Bioscience, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Survival disparities among Asian, Native Hawaiian and Pacific Islander (ANHPI) patients with non-Hodgkin lymphoma (NHL) in the United States - Chun-Pin Esther Chang; Jing Wang; Catherine Lee; Mia Hashibe (Cancer Causes & Control, 2025)

Exploring the oral bacteria-oral lichen planus connection: mechanisms, clinical implications and future directions - Wei-long Zhang; Lian-pin Yu; Wei Zhou; Xue Wang; Juan Du (Archives of Microbiology, 2025)

Geoarchaeological study of the evolution of rice farming fields in prehistoric Yangtze Delta and Huai River regions of China - Yijie Zhuang; Pin Ding; Lina Zhuang; Yonglei Wang; Wenwan Wu; Xia Wang; Yulong Niu; Guoping Sun; Xingtao Wei; Ling Qin (Quaternary Science Reviews, 2025)

The influence of corona sheath conductivity distribution on the transmission characteristics of return-stroke currents - Pin Lv; Wangsheng Wang; Ping Yuan; Yingying An; Tingting An; Hong Deng; Lizhen Yuan (Atmospheric Research, 2025)

Immune response to polystyrene microplastics: Regulation of inflammatory response via the ROS-driven NF-κB pathway in zebrafish (Danio rerio) - Jincheng Pei; Shannan Chen; Qingxia Ke; Anning Pang; Mengmeng Niu; Nan Li; Jiayi Li; Zhi Wang; Hongjuan Wu; Pin Nie (Aquatic Toxicology, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Spatial-confined CuCo bimetallic nanoparticles in nitrogen-doped carbon flowers enable low-input/input-free electrocatalytic hydrogen production - Fenghua Ge; Mengjiao Guo; Xu Dong; Fengcai Lei; Junfeng Xie; Qikun Zhang; Zhihua Li; Qian Wang; Pin Hao (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Impact of emerging technologies on corporate social responsibility in mining industry - Muhammad Haroon; Mirzat Ullah; Zhanqiang Li; Shuo Zhu; Judong Wang; Chu-Pin (Eugune) Hsueh (Resources Policy, 2025)

TiO2 mesocrystal reactive electrochemical membrane for rapid removal of organic pollutants from bio-treated coking wastewater - Weiyi Wang; Yanxi Gong; Jianbing Wang; Huijiao Wang; Chunrong Wang; Pin Hou; Chunhui Zhang (Process Safety and Environmental Protection, 2025)

Microplastic types dominate the effects of bismuth oxide semi-conductor nanoparticles on their transport in saturated quartz sand - Lin Xu; Shaoyan Lv; Quanyuan Chen; Pin Gao; Genyao Gu; Yongxia Wang; Xiaopeng Min; Hyunjung Kim; Li Cai (Journal of Hazardous Materials, 2025)

Molecular characterization of TRAF gene family in snakehead (Channa argus) - Xiu Feng Han; Ming Yue Che; Xue Su; Jing Yun Tian; Lan Hao Liu; Pin Nie; Su Wang (Fish & Shellfish Immunology, 2025)

A novel MOF-on-MOF-derived carbon-encapsulated CeO2/Co/Co3O4 humidity-resistant heterojunction with abundant oxygen vacancies for efficient ozone removal - Abiyu Kerebo Berekute; An-Yu Wang; Kun-Yi Lin; Sepridawati Siregar; Kuo-Pin Yu (Environmental Research, 2025)

Oligosaccharide-assisted resolution of holothurian fucosylated chondroitin sulfate for fine structure and P-selectin inhibition - Ying Pan; Huifang Sun; Xi Gu; Sujuan Li; Shengtao Yang; Liang Zhang; Hui Mao; Pin Wang; Shasha Yang; Ronghua Yin; Zhili Zuo; Jinhua Zhao (Carbohydrate Polymers, 2025)

An optimized non-landslide sampling method for Landslide susceptibility evaluation using machine learning models - Shuai Xu; Yingxu Song; Pin Lu; Guizhen Mu; Ke Yang; Shangxiao Wang (Natural Hazards, 2025)

A novel application of slow-release fertilizers in fertilizer-drawn forward osmosis for real domestic wastewater treatment - Chenchen Li; Pin Zhao; Zunaira Habib; Weilong Song; Xinhua Wang (Journal of Water Process Engineering, 2025)

Role of the clock gene period in regulating circadian rhythm of courtship vibrations in Nilaparvata lugens - Qi Wei; Jia-Chun He; Wei-Xia Wang; Feng-Xiang Lai; Pin-Jun Wan; Qiang Fu (Insect Biochemistry and Molecular Biology, 2025)

Recent advances in immobilization of heavy metals from municipal solid waste incineration fly ash - Rahul Karyappa; Pin Jin Ong; Jie Bu; Longgang Tao; Qiang Zhu; Cun Wang (Fuel, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Microplastics accelerate nitrification, shape the microbial community, and alter antibiotic resistance during the nitrifying process - Yang Wang; Peikun Yuan; Pin Gao (Science of The Total Environment, 2025)

Iron/nitrogen/sulfur co-doped cyanobacteria derived carbon composites for enhanced hydroxychloroquine degradation via primary nonradical pathway in peroxymonosulfate-based fenton-like system - Tao Wang; Yuxuan Yang; Zheren Tang; Pin Zhao; Kunlun Yang; Xinhua Xu (Journal of Cleaner Production, 2025)

Life cycle assessment of CO2 capture through pressure swing adsorption using MOF-74 - Pin Wang; Zhen Pan; Zhiming Liu; Liyan Shang; Mohamad Reza Soltanian; Zhien Zhang (Gas Science and Engineering, 2025)

Rheology, stability, and physicochemical properties of NaOH-tannic acid solvent for β-chitin dissolution - Shang-Ta Wang; Po-Jou Huang; Szu-Kai Chen; Chia-Rui Shen; Yi-Pin Chen; Min-Lang Tsai (Food Hydrocolloids, 2025)

Rich molecular diversity of ribosomal RNA genes in Pseudo-nitzschia species (Bacillariophyceae) revealed through single-strain high throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Chui Pin Leaw; Nansheng Chen (Algal Research, 2025)

Evaluation and mitigation of potentially toxic elements contamination in mangrove ecosystem: Insights into phytoremediation and microbial perspective - Gobinda Dey; Jyoti Prakash Maity; Pritam Banerjee; Raju Kumar Sharma; Koyeli Das; Gopalakrishnan Gnanachandrasamy; Chin-Wen Wang; Pin-Yun Lin; Shan-Li Wang; Chien-Yen Chen (Marine Pollution Bulletin, 2024)

Research on the optimal pick-up heights and their control strategy for the hydraulic double-row jet collector of the manganese nodule miner - Pin-Jian Wang; Li Li; Dong-Chao Xie; Mi-Qian Fan; Jia-Bin Wu (Ocean Engineering, 2024)

A 2D/3D hierarchical hybrid enables energy-saving hydrogen production coupled with glycerol and urea electro-oxidation - Ziyu Zhou; Fenghua Ge; Ruirui Xu; Xu Dong; Mengjiao Guo; Guanwei Cui; Qian Wang; Pin Hao (Journal of Environmental Chemical Engineering, 2024)

Inhibitory effects of cold plasma-activated water on the generation of advanced glycation end products and methylimidazoles in cookies and mechanistic evaluation using electron paramagnetic resonance - Chenxia Zhang; Jian Zhang; Tiantian Huang; Pin Jiang; Xuejiao Qie; Lan Mo; Maiquan Li; Aihua Lou; Qingwu Shen; Jie Luo; Shuai Wang; Yi XueC; et al. (Food Chemistry, 2024)

Treatment of various saline wastewaters by membrane distillation with omniphobic polyvinyl alcohol membrane - Chenshuo Wang; Lie Liu; Yuxiang Wang; Pin Hou; Jianbing Wang; Jun Wang (Desalination, 2024)

The Effect of Platelet Fibrin Plasma (PFP) on Postoperative Refractory Wounds: Physiologically Concentrated Platelet Plasma in Wound Repair - Lu Fan; Ying Zhang; Xiankun Yin; Silu Chen; Pin Wu; Tianru Huyan; Ziyang Wang; Qun Ma; Hua Zhang; Wenhui Wang; Chunyan Gu; Lu Tie; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Projected population exposure to precipitation extremes in China by the end of the twenty-first century: trends, change points, and spatial variability - Yue Sheng; Chenghua Shen; Yao Li; Pin Wang; Tangao Hu (Regional Environmental Change, 2024)

The Influence of the COVID-19 Pandemic on Pseudomonas aeruginosa Infection in Children, Henan, China - Mengxin Zhang; Meng Sun; Pin Zhang; Ligong Hou; Bang Du; Huanmin Wang; Xianwei Zhang; Wancun Zhang (Indian Journal of Microbiology, 2024)

Taiwan’s mysterious mollusks: a deep dive into the cryptic hybridization of Pomacea canaliculata and Pomacea maculata - Pritam Banerjee; Nalonda Chatterjee; Kathryn A. Stewart; Jung-Sheng Chen; Gobinda Dey; Jyoti Prakash Maity; Raju Kumar Sharma; Chin-Wen Wang; Pin-Yun Lin; Kuan Hsien Lee; Chien-Yen Chen (Evolutionary Ecology, 2024)

Peteryoungia algae sp. nov. isolated from seaweeds of Gouqi Island, China, and its unique genetic features among Peteryoungia strains - Jun Yin; Min He; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Gen Chen; Ze-Fei Wang; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Antonie van Leeuwenhoek, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Terrestrial support of wetland food webs via a dissolved inorganic carbon pathway - Junna Wang; John R. Durand; Sharon P. Lawler; Pin‐Yuan Chen; Xiaoli Dong (Limnology and Oceanography, 2024)
Studies of terrestrial support of aquatic food webs have focused primarily on terrestrial organic matter (t‐OM) directly used by animal and microbial consumers. However, dissolved inorganic carbon (DIC) released from t‐OM might also support aquatic primary producers, a key resource for zooplankton and upper trophic levels. Using 2‐yr 13 C measurements of algae, zooplankton, terrestrial detritus, sediments, dissolved and particulate organic matter from six seasonal wetlands, we found that in January when algal concentration was low, zooplankton used t‐OM directly or heterotrophic microbes that decompose t‐OM, but in March and May zooplankton was mainly supported by algae as their basal resources, and the algae used DIC derived from the mineralization and methanogenesis of t‐OM, suggesting the DIC pathway of terrestrial support of aquatic food webs. The decomposition of abundant t‐OM from both bed sediments and water column caused high concentrations of DIC. Despite uptake by algae, about half of DIC produced in January and March ended up as emissions to the atmosphere in the form of CO 2 . This finding revealed the dual roles of t‐OM in maintaining the productivity and stability of aquatic food webs and in contributing to global carbon emissions. This duality poses challenges for simultaneously mitigating carbon emissions and conserving biological communities in seasonal wetlands. Finally, wide seasonal differences in δ 13 C in DIC (−12.4‰ to 6.7‰) were observed, mainly driven by air–water CO 2 exchange and photosynthesis, suggesting that 13 C may be a powerful tool to investigate carbon cycling in shallow, temporary freshwater ecosystems that are widespread but understudied.

Towards automatic urban tree inventory: Enhancing tree instance segmentation via moving object removal and a chord length-based DBH estimation approach - Wai Yi Chau; Jun Kang Chow; Tun Jian Tan; Jimmy WU; Mei Ling Leung; Pin Siang Tan; Siu Wai Chiu; Billy Chi Hang Hau; Hok Chuen Cheng; Yu-Hsing Wang (Computers and Electronics in Agriculture, 2024)

Revisiting the chloramination of phenolic compounds: Formation of novel high-molecular-weight nitrogenous disinfection byproducts - Pin Wang; Bei Ye; Youhei Nomura; Taku Fujiwara (Water Research, 2024)

Projecting urban flood risk through hydrodynamic modeling under shared socioeconomic pathways - Yihan Lou; Pin Wang; Yao Li; Yindong Zhang; Bin Xie; Tangao Hu (Journal of Environmental Management, 2024)

On-device charge engineering in 2D perovskite oxides for high performance photodetectors - Yong Zhang; Lin Wang; Xiujun Wang; Xiaohang Pan; Pin Zhao; Ye Liu; Qing Guo; Lixing Kang; Xiaosheng Fang (Chemical Engineering Journal, 2024)

New insights into biofouling worsening induced by salinity stress in membrane bioreactor: Response of quorum sensing system and its regulation role - Weilong Song; Huaning Wu; Enyu Liu; Boyan Xu; Pin Zhao; Xinhua Wang; How Yong Ng (Chemical Engineering Journal, 2024)

Emerging transition metal sulfide/MXene composites for the application of electrochemical energy storage - Xianghui Hu; Pin Ma; Zehao Zhang; Jian Wang; Cheng Li; Yee Sin Ang; Haibo Li; Hui Ying Yang (Chemical Engineering Journal, 2024)

Predicting increments in heavy metal contamination in farmland soil - Jieh-Haur Chen; Meng-Fen Yeh; Jui-Pin Wang; Hsi-Hsien Wei (Environment, Development and Sustainability, 2024)

Impact of polystyrene nanoplastics on apoptosis and inflammation in zebrafish larvae: Insights from reactive oxygen species perspective - Jincheng Pei; Shannan Chen; Li Li; Kailun Wang; Anning Pang; Mengmeng Niu; Xueyun Peng; Nan Li; Hongjuan Wu; Pin Nie (Science of The Total Environment, 2024)

Nanoplastics composite norfloxacin induced changes in conformation and function of lysozyme and differential effects of co-exposure contamination - Hengyu Song; Pin Jiang; Houquan Tang; Zaifeng Wang; Xuan Ge; Xiangxiang Li; Falin He; Shuqi Guo; Guang Tian; Yuntao Qi; Shaoyang Hu; Rutao Liu (Science of The Total Environment, 2024)

Removal of cyanide by peroxydisulfate activated by copper ions inherently present in the electroplating wastewater - Zih-Syuan Wang; Yi-Chin Cho; Yi-Pin Lin (Journal of Environmental Chemical Engineering, 2024)

Structural characterization and hypoglycemic activity of Cordyceps sinensis polysaccharide (CSP-3) - Pin Gong; Yingying Ke; Xiaojuan Wang; Hui Long; Wenjuan Yang; Jing Wang; Nan Li; Yanni Zhao; Fuxin Chen; Yuxi Guo (Food Bioscience, 2024)

Poly (ionic liquid) anchored granular activated carbon for efficient and selective removal of perchlorate: performance, DFT calculations and mechanism - Pin Hou; Xinyu Sun; Jianhui Guo; Chunrong Wang; Cesar Nieto-Delgado; Jianbing Wang (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Innovative and versatile surface-enhanced Raman spectroscopy-inspired approaches for viral detection leading to clinical applications: A review - Jaya Sitjar; Jiunn-Der Liao; Han Lee; Huey-Pin Tsai; Jen-Ren Wang (Analytica Chimica Acta, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Structurally tuned polyamide membranes via the polyvinylpyrrolidone-modulated interfacial polymerization reaction for enhanced forward osmosis performance - Yao Jiang; Pin Zhao; Subo Xu; Hao Liu; Wenyan Zhang; Weilong Song; Xinhua Wang (Desalination, 2024)

Detection of a mud volcano in the Weitan Banks area of the northern South China Sea - Wei Luo; Pin Yan; Yanlin Wang; Junhui Yu; Qionghua Wan; Zhenbo Zhang; Tao Xue (Journal of Oceanology and Limnology, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Targeted delivery of food functional ingredients in precise nutrition: design strategy and application of nutritional intervention - Xu Wang; Guohua Shi; Sufang Fan; Junmei Ma; Yonghuan Yan; Mengtian Wang; Xiaozhi Tang; Pin Lv; Yan Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Chromosome-Level Genome Assembly and Comparative Genomic Analysis of the Barbel Chub (Squaliobarbus curriculus) by Integration of PacBio Sequencing and Hi-C Technology - Baidong Zhang; Yanling Sun; Yang Liu; Xiaojun Song; Su Wang; Tiaoyi Xiao; Pin Nie (Fishes, 2024)
The barbel chub (Squaliobarbus curriculus), the only species in the genus, is widely distributed in freshwater lakes and rivers at different latitudes in East Asia, with fishery and biodiversity importance, and is an emerging commercially important fish in China. However, the resource of this species has dramatically declined due to anthropogenic activities such as over-exploitation, as well as water pollution. Genomic resources for S. curriculus are useful for the management and sustainable utilization of this important fish species, and also for a better understanding of its genetic variation in the region. Here, we report the chromosome-level assembly of the S. curriculus genome obtained from the integration of PacBio long sequencing and Hi-C technology. A total of 155.34 Gb high-quality PacBio sequences were generated, and the preliminary genome assembly was 894.95 Mb in size with a contig N50 being 20.34 Mb. By using Hi-C data, 99.42% of the assembled sequences were anchored to 24 pseudochromosomes, with chromosome lengths ranging from 27.22 to 58.75 Mb. A total of 25,779 protein-coding genes were predicted, 94.70% of which were functionally annotated. Moreover, S. curriculus shows resistance to grass carp haemorrhagic disease (GCHD) caused by grass carp reovirus (GCRV), which seriously hinders the status and future perspectives of commercial grass carp production. Phylogenetic analysis indicated that S. curriculus diverged with grass carp (Ctenopharyngodon idellus) approximately 20.80 million years ago. Annotations of the expanded gene families were found to be largely enriched in immune-related KEGG pathway categories. Moreover, a total of 18 Toll-like receptor (TLR) genes were identified from the whole genome of S. curriculus. The high-quality genome assembled in this study will provide a valuable resource for accelerating ecological, evolutionary, and genetic research on S. curriculus.

Nitrogen addition alleviates water loss of Moso bamboo (Phyllostachys edulis) under drought by affecting light-induced stomatal responses - Xi-pin Wu; Xiaomin Gao; Ruichang Zhang; Junwei Luan; Yi Wang; Shirong Liu (Science of The Total Environment, 2024)

Wildfire-vegetation-climate-human interactions in the central Taiwan region during 17.3–2.0 cal kyr BP, inferred from sediments of Toushe Basin - Abdur Rahman; Yuan-Pin Chang; Hong-Chun Li; Ling-Ho Chung; Yu-Min Chou; Liang-Chi Wang (Quaternary Science Reviews, 2024)

Novel multi-spatial receptive field (MSRF) XGBoost method for predicting geological cross-section based on sparse borehole data - Yashi Qiu; Ning Zhang; Zhenyu Yin; Yu Wang; Changjie Xu; Pin Zhang (Engineering Geology, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

1300-m-High gas plume from pockmarks in the north Nansha waters, South China sea - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Jinfeng Ma; Zhuangcai Tian; Changliang Chen (Marine and Petroleum Geology, 2024)

The combination of high temperature and Vibrio infection worsens summer mortality in the clam Meretrix petechialis by increasing apoptosis and oxidative stress - Jing Tian; Di Wang; Hongxia Wang; Pin Huan; Baozhong Liu (Fish & Shellfish Immunology, 2024)

MYPT1SMKO Mice Function as a Novel Spontaneous Age- and Hypertension-Dependent Animal Model of CSVD - Jian Chen; Cheng-Gang Li; Li-Xuan Yang; Yi Qian; Li-Wen Zhu; Pin-Yi Liu; Xiang Cao; Ye Wang; Min-Sheng Zhu; Yun Xu (Translational Stroke Research, 2024)

New insights on destruction mechanisms of waste activated sludge during simultaneous thickening and digestion process via forward osmosis membrane - Xiawen Yi; Zhiwei Wang; Pin Zhao; Weilong Song; Xinhua Wang (Water Research, 2024)

Seg2Tunnel: A hierarchical point cloud dataset and benchmarks for segmentation of segmental tunnel linings - Wei Lin; Brian Sheil; Pin Zhang; Biao Zhou; Cheng Wang; Xiongyao Xie (Tunnelling and Underground Space Technology, 2024)

Late Holocene paleoclimate reconstruction of northern Taiwan using a multiproxy approach in the Dream Lake sediment core - Abdur Rahman; Wei-Cheng Chang; Kaoru Kashima; Yu Fukumoto; Jyh-Jaan Steven Huang; Ludvig Löwemark; Liang-Chi Wang; Yuan-Pin Chang (Quaternary International, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

CFD-DEM-based evaluation of main-channel sediment transport processes subject to supplement from a steep tributary - Yi-Pin Nie; Xie-Kang Wang; Xu-Feng Yan (Engineering Geology, 2024)

Mo, N co-doped cobalt hydroxide nanosheets for highly selective methanol-to-formate electrocatalytic conversion - Yaoxin Wu; Lili Ban; Hanzhen Wang; Qian Yang; Yaao Li; Ke Lu; Yuxiang Li; Pin Cui; Jinfeng Yang; Dalei Chang; Dezheng Yang; Feng Yu; et al. (Chemical Engineering Journal, 2024)

Anaerobic acidification membrane bioreactor operating at acidic condition for treating concentrated municipal wastewater: Performance and implication - Huihui Zhong; Qiming Wang; Mengfei Wu; Pin Zhao; Weilong Song; Xinhua Wang (Bioresource Technology, 2024)

The health risk reduction of PM2.5 via a green curtain system in Taiwan - Yi Hsing Chang; Ting-Hsuan Chen; Hsin-Ying Chung; Hsi-Yu Hsiao; Pin-Chieh Tseng; Yu-Chun Wang; Shih-Chun Candice Lung; Huey-Jen Su; Yaw-Shyan Tsay (Building and Environment, 2024)

Nuclear Factor Erythroid 2-Related Factor 2 is Essential for Low-Normobaric Oxygen Treatment-Mediated Blood-Brain Barrier Protection Following Ischemic Stroke - Xiao-Xiao Ma; Hai-Yi Xie; Pin-Pin Hou; Xiao-Jing Wang; Wei Zhou; Zhen-Hong Wang (Molecular Neurobiology, 2024)

Extensive intragenomic variations of the 18S rDNA V4 region in the toxigenic diatom species Pseudo-nitzschia multistriata revealed through high-throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Zhangxi Hu; Weizhou Chen; Chui Pin Leaw; Nansheng Chen (Marine Pollution Bulletin, 2024)

The establishment and evaluation of a swine model of deinagkistrodon acutus snakebite envenomation - Linjie Lai; Lutao Xie; Yi Chen; Wang Du; Xuelin Yang; Wanjuan Liu; Peixin Shangguan; Jiefeng Xu; Pin Lan (Toxicon, 2024)

Numerical study on the structural performances of the collector of the polymetallic nodule mining vehicle under different operating modes - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2024)

Comprehensive Multi-omics Approaches Provide Insights to Summer Mortality in the Clam Meretrix petechialis - Jing Tian; Hongxia Wang; Pin Huan; Xin Yue; Baozhong Liu (Marine Biotechnology, 2024)

Numerical investigation of the hydrodynamic characteristics of the polymetallic nodule miner considering the internal fluid field - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2024)

Valorization of coconut peat to develop a novel shape-stabilized phase change material for thermal energy storage - Pin Jin Ong; Si Hui Angela Goh; Yihao Leow; Suxi Wang; Pei Wang; Zibiao Li; Xuesong Yin; Beng Hoon Tan; Warintorn Thitsartarn; Jianwei Xu; Xian Jun Loh; Dan Kai; et al. (Journal of Cleaner Production, 2024)

The employment of self-awareness in investigating public willingness to implement low-carbon: The application of labeling theory - Kuei-Feng Chang; I-Tung Shih; Pin-Huan Wang (Journal of Cleaner Production, 2024)

Economical-effective purification of brackish water through an integrated capacitive desalination & boron adsorption system - Liping Yang; Yixiang Li; Lu Guo; Pin Ma; Zhi Yi Leong; Jing Wang; Hui Ying Yang (Desalination, 2024)

Modification of grilles to improve the lavatory environment on an aircraft - Tengfei (Tim) Zhang; Pin Li; Chao-Hsin Lin; Feng Wang (Building and Environment, 2024)

The Influences of the COVID-19 Pandemic on Haemophilus parainfluenzae Infection in Children, Henan, China, 2016–2021 - Mengxin Zhang; Meng Sun; Pin Zhang; Huanmin Wang; Xianwei Zhang; Wancun Zhang (Indian Journal of Microbiology, 2024)

Novel and continuous scientific and technical breakthroughs increase value and efficiency in aquaculture - Qingchao Wang; Pin Nie (Reviews in Aquaculture, 2024)

An overview of microplastic pollution in the environment over the megacity of Shanghai during 2013–2022 - Peikun Yuan; Yang Wang; Xiaoqian Chen; Pin Gao (Science of The Total Environment, 2024)

Boosting algicidal efficiency of Alteromonas sp. FDHY-CJ against Skeletonema costatum through fermentation optimization - Pin Lv; Xinguo Shi; Qianqian Wang; Yuying Zhong; Yisong Guo; Jianfeng Chen (Protist, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Contributions of climate change and urbanization to urban flood hazard changes in China's 293 major cities since 1980 - Ziyi Tang; Pin Wang; Yao Li; Yue Sheng; Ben Wang; Nataliia Popovych; Tangao Hu (Journal of Environmental Management, 2024)

Management of the designed risk level of urban drainage system in the future: Evidence from haining city, China - Yihan Lou; Pin Wang; Yao Li; Luoyang Wang; Chaohui Chen; Jiahui Li; Tangao Hu (Journal of Environmental Management, 2024)

Simultaneous removal of organic micropollutants and metals from water by a multifunctional β-cyclodextrin polymer-supported-polyaniline composite - Pin Wang; Guangyu An; Peter Jarvis; Wen Liu; Shunke Ding; Ruixin Qu; Zhanghan Li; Cheng Ye; Wenhai Chu (Chemical Engineering Journal, 2024)

Bifunctional drug delivery system with carbonic anhydrase IX targeting and glutathione-responsivity driven by host-guest amphiphiles for effective tumor therapy - Jiawei Zhou; Yamin Li; Lutao Wang; Pin Lv; Miao Chen; Feijian Xiao; Tian Si; Jun Tao; Bo Yang (Carbohydrate Polymers, 2024)

Intra-subject enveloped multilayer fuzzy sample compression for speech diagnosis of Parkinson's disease - Yiwen Wang; Fan Li; Xiaoheng Zhang; Pin Wang; Yongming Li; Yanling Zhang (Medical & Biological Engineering & Computing, 2024)

Assessment of sediment transport in Luxiapuqu watershed using RUSLE-TLSD and InSAR techniques: Yarlung Tsangpo River, China - Hao-Shuang Chen; Ling Lan; Yi-Pin Nie; Yu-Ge Wang; Xie-Kang Wang (Environmental Science and Pollution Research, 2024)

Subsurface structures and nature of seafloor mounds in the northern South China Sea margin: Implications for Mesozoic hydrocarbon exploration - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Geomorphology, 2024)

Activation of peroxymonosulfate by sewage sludge-derived biochar to promote short-chain fatty acid production during sludge anaerobic fermentation - Jinling He; Qingchen Wu; Nan Jiang; Ai Zhang; Lin Wang; Xiang Li; Gang Xue; Hong Chen; Pin Gao (Chemical Engineering Journal, 2024)

Molecular simulation of the dynamic distribution of complex oil components in shale nanopores during CO2-EOR - Tao Huang; Linsong Cheng; Renyi Cao; Xiaobiao Wang; Pin Jia; Chong Cao (Chemical Engineering Journal, 2024)

Coded-Aperture imaging based on random code and Backpropagation neural network - Zeyu Wang; Chao Wang; Pin Gong; Liansheng Li; Zhimeng Hu; Yongqiang Shi; Xiaolei Shen; Cheng Zhou; Xiaoxiang Zhu; Xiaobin Tang (Annals of Nuclear Energy, 2024)

Normal fault evolution in the Penghu Basin, a Paleogene Rift Basin in Western Taiwan Strait: A test of fault growth models - Pin-Rong Wu; Kenn-Ming Yang; Pin-Chi Wang; Chang-Jie Lee; Jong-Chang Wu (Tectonophysics, 2023)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Association of co-exposure to metal(loid)s during pregnancy with birth outcomes in the Tibetan plateau - Lei Zhao; Tiemei Li; Haijing Wang; Yue-Mei Fan; Yuancan Xiao; Xuejun Wang; Shulin Wang; Pin Sun; Pinhua Wang; Zhaxi Jiangcuo; Li Tong; Liehong Wang; et al. (Chemosphere, 2023)

Polymeric PDI-based photocatalytic nanoarchitectures promoting the performance of thin film composite membrane for forward osmosis water purification - Pin Zhao; Yang Hu; Xiaoqiang An; Rong Ji; Hao Liu; Hui Zhao; Weilong Song; Yuming Dong; Xinhua Wang (Chemical Engineering Journal, 2023)

Integrating anaerobic acidification with two-stage forward osmosis concentration for simultaneously recovering organic matter, nitrogen and phosphorus from municipal wastewater - Siyi Chen; Zunaira Habib; Zhiwei Wang; Pin Zhao; Weilong Song; Xinhua Wang (Water Research, 2023)

Metal ion assistant transformation strategy to synthesize catechol-based metal–organic frameworks from Ti3C2T precursors - Weikang Wang; Yan Bai; Pin Yang; Shuai Yuan; Feiyang Li; Weiwei Zhao; Beibei Jin; Xuan Zhang; Shujuan Liu; Daqiang Yuan; Qiang Zhao (Science Bulletin, 2023)

Cationic segregation of Ca2Mn3O8 enabling high selectivity for fluoride ions through capacitive deionization - Wei Wang; Pin Ma; Haibo Li (Desalination, 2023)

Unveiling the fates of nitro-transformation products in advanced oxidation process: A DFT-based kinetic model - Pin Wang; Lingjun Bu; Lu Luo; Yangtao Wu; Weiqiu Zhang; Shiqing Zhou; John C. Crittenden (Chemical Engineering Journal, 2023)

Impact of Taiwan’s 2021 COVID-19 lockdown on the symptom severity and quality of life of patients with narcolepsy - Wei-Chih Chin; Yu-Shu Huang; I. Tang; Pin-Yi Lee; Chih-Huan Wang; Kuo-Yu Chao (Sleep and Biological Rhythms, 2023)

TAT-PEP Alleviated Cognitive Impairment by Alleviating Neuronal Mitochondria Damage and Apoptosis After Cerebral Ischemic Reperfusion Injury - Pin Zhao; Jiapo Zhang; JianKe Kuai; Liya Li; Xuying Li; Namin Feng; Hailiang Du; Chen Li; Qiang Wang; Bin Deng (Molecular Neurobiology, 2023)
Paired immunoglobulin-like receptor B (PirB) was identified as a myelin-associated inhibitory protein (MAIP) receptor that plays a critical role in axonal regeneration, synaptic plasticity and neuronal survival after stroke. In our previous study, a transactivator of transcription-PirB extracellular peptide (TAT-PEP) was generated that can block the interactions between MAIs and PirB. We found that TAT-PEP treatment improved axonal regeneration, CST projection and long-term neurobehavioural recovery after stroke through its effects on PirB-mediated downstream signalling. However, the effect of TAT-PEP on the recovery of cognitive function and the survival of neurons also needs to be investigated. In this study, we investigated whether pirb RNAi could alleviate neuronal injury by inhibiting the expression of PirB following exposure to oxygen–glucose deprivation (OGD) in vitro. In addition, TAT-PEP treatment attenuated the volume of the brain infarct and promoted the recovery of neurobehavioural function and cognitive function. This study also found that TAT-PEP exerts neuroprotection by reducing neuronal degeneration and apoptosis after ischemia–reperfusion injury. In addition, TAT-PEP improved neuron survival and reduced lactate dehydrogenase (LDH) release in vitro. Results also showed that TAT-PEP reduced malondialdehyde (MDA) levels, increased superoxide dismutase (SOD) activity and reduced reactive oxygen species (ROS) accumulation in OGD-injured neurons. The possible mechanism was that TAT-PEP could contribute to the damage of neuronal mitochondria and affect the expression of cleaved caspase 3, Bax and Bcl-2. Our results suggest that PirB overexpression in neurons after ischaemic-reperfusion injury induces neuronal mitochondrial damage, oxidative stress and apoptosis. This study also suggests that TAT-PEP may be a potent neuroprotectant with therapeutic potential for stroke by reducing neuronal oxidative stress, mitochondrial damage, degeneration and apoptosis in ischemic stroke.

AI-IoT integrated framework for tree tilt monitoring: A case study on tree failure in Hong Kong - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau (Agricultural and Forest Meteorology, 2023)

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

Genesis of ferromanganese nodules associated with mud volcanoes in the southeastern Dongsha waters of the northern South China Sea: Implications for regional deep Mesozoic hydrocarbon prospects - Yunfan Zhang; Pengchun Li; Yongbin Jin; Xingjian Liu; Yanlin Wang; Pin Yan; Guangjian Zhong; Yunying Zhang (Marine and Petroleum Geology, 2023)

Discrete element modelling of thermal penetration test with heating and cooling - Pin-Qiang Mo; Jing Hu; Yu-Chen Hu; Kuan-Jun Wang; Abolfazl Eslami; Liu Gao (Computers and Geotechnics, 2023)

Arginase from Priestia megaterium and the Effects of CMCS Conjugation on Its Enzymological Properties - Yu Liang Jiao; Pin Quan Shen; Shu Fang Wang; Jing Chen; Xiang Hong Zhou; Gui Zhen Ma (Current Microbiology, 2023)

Highly-specific aptamer targeting SARS-CoV-2 S1 protein screened on an automatic integrated microfluidic system for COVID-19 diagnosis - Hung-Bin Wu; Chih-Hung Wang; Yi-Da Chung; Yan-Shen Shan; Ying-Jun Lin; Huey-Pin Tsai; Gwo-Bin Lee (Analytica Chimica Acta, 2023)

Predictive models for the aqueous phase reactivity of inorganic radicals with organic micropollutants - Pin Wang; Lingjun Bu; Shiqing Zhou; Yangtao Wu; Lin Deng; Zhou Shi (Chemosphere, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Identification of key precursors contributing to the formation of CX3R-type disinfection by-products along the typical full-scale drinking water treatment processes - Xu Yang; Shunke Ding; Rong Xiao; Pin Wang; Zhenqi Du; Ruihua Zhang; Wenhai Chu (Journal of Environmental Sciences, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

Rational targeting of autophagy in colorectal cancer therapy: From molecular interactions to pharmacological compounds - Canhui Jin; Tianbao Wang; Yanhui Yang; Pin Zhou; Juncheng Li; Wenhao Wu; Xin Lv; Guoqing Ma; Aihong Wang (Environmental Research, 2023)

A Novel Approach to Three-Dimensional Inference and Modeling of Magma Conduits with Exploration Data: A Case Study from the Jinchuan Ni–Cu Sulfide Deposit, NW China - Xiancheng Mao; Pin Liu; Hao Deng; Zhankun Liu; Longjiao Li; Yushan Wang; Qixing Ai; Jianxin Liu (Natural Resources Research, 2023)

Exploring economic and environmental efficiency in renewable energy utilization: a case study in the Organization for Economic Cooperation and Development countries - Chia-Nan Wang; Thi Thanh Tam Nguyen; Thanh-Tuan Dang; Hsien-Pin Hsu (Environmental Science and Pollution Research, 2023)

Detection of live SARS-CoV-2 virus and its variants by specially designed SERS-active substrates and spectroscopic analyses - Jaya Sitjar; Jiunn-Der Liao; Han Lee; Huey-Pin Tsai; Jen-Ren Wang; Chien-Hsiung Chen; Hao Wang; Bernard Haochih Liu (Analytica Chimica Acta, 2023)

Future changes in urban drainage pressure caused by precipitation extremes in 285 cities across China based on CMIP6 models - Pin Wang; Yao Li; Jinjin Fan; Feng Kong; Dengrong Zhang; Tangao Hu (Sustainable Cities and Society, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

High-Fat Diet Exacerbates Autistic-Like Restricted Repetitive Behaviors and Social Abnormalities in CC2D1A Conditional Knockout Mice - Yu-Chiao Wang; Chin-Hao Chen; Cheng-Yi Yang; Pin Ling; Kuei-Sen Hsu (Molecular Neurobiology, 2023)

Origin of a giant fuzzy reflection zone and its implication for natural gas exploration in the southwestern Qiongdongnan Basin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Yan Qiu; Guanghong Tu; Changliang Chen (Journal of Oceanology and Limnology, 2023)

Discovery of pockmarks in the Zengmu Basin, southern South China Sea and the implication - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Yongbin Jin; Changliang Chen; Jie Liu (Journal of Oceanology and Limnology, 2023)

Evolution of micro-damage and degradation of macro-mechanical properties of sandstone due to thermal effects - Pin Wang; Tubing Yin; Xibing Li; Heinz Konietzky (Bulletin of Engineering Geology and the Environment, 2023)

Nitrogen addition alleviates drought effects on water status and growth of Moso bamboo (Phllostachys edulis) - Xi-Pin Wu; Shirong Liu; Junwei Luan; Yi Wang; Xiaomin Gao; Chen Chen (Forest Ecology and Management, 2023)

Single-atom Mn anchored on N-doped graphene oxide for efficient adsorption-photocatalytic degradation of sulfanilamide in water: Electronic interaction and mineralization pathway - Honghong Lyu; Pin Li; Jingchun Tang; Weixin Zou; Pengfei Wang; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Indoor and roadside exposures to traffic noise and cardiovascular mortality and the role of urban environmental stressors across a high-rise, high-density environment: A case study in Hong Kong - Pin Wang; Haipei Xiang; Mengdi Guo; Yuan Shi; Ka Chun Chong; Jianxiang Huang; Hung Chak Ho (Building and Environment, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Carbon emission reduction policy with privatization in an oligopoly model - Junlong Chen; Chaoqun Sun; Yajie Wang; Jiali Liu; Pin Zhou (Environmental Science and Pollution Research, 2023)

Geophysical evidence for a serpentine mud volcano in the relict slow-spreading center of the South China Sea - Yanlin Wang; Pin Yan; Junhui Yu; Guanghong Tu; Jun Wang; Yan Qiu; Changliang Chen (Tectonophysics, 2023)

Geomorphic development of an unvegetated shingle cay on the Ximen Reef in the southern South China Sea - Shengnan Zhou; Qi Shi; Hongqiang Yang; Lirong Wang; Xiyang Zhang; Xiaoju Liu; Fei Tan; Pin Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Research on the lightweight structural optimization design of the front collector of the polymetallic nodule miner - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2023)

Investigating relationships between landscape patterns and surface runoff from a spatial distribution and intensity perspective - Luoyang Wang; Hao Hou; Yao Li; Jing Pan; Pin Wang; Ben Wang; Jie Chen; Tangao Hu (Journal of Environmental Management, 2023)

Hypervalent potassium xanthate modified SnO2 for highly efficient perovskite solar modules - Pin Lv; Yufei Yang; Neng Li; Yuxi Zhang; Min Hu; Bo Huang; Yanqing Zhu; Yulong Wang; Junye Pan; Shifeng Wang; Bo Zhang; Fuzhi Huang; et al. (Chemical Engineering Journal, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Analyzing spatial variance of urban waterlogging disaster at multiple scales based on a hydrological and hydrodynamic model - Luoyang Wang; Yao Li; Hao Hou; Yan Chen; Jinjin Fan; Pin Wang; Tangao Hu (Natural Hazards, 2022)

Integrating AIS, GIS and E-Chart to Analyze the Shipping Traffic and Marine Accidents at the Kaohsiung Port - Chien-Chang Chou; Chia-Nan Wang; Hsien-Pin Hsu; Ji-Feng Ding; Wen-Jui Tseng; Chien-Yi Yeh (Journal of Marine Science and Engineering, 2022)
In the past, case study and questionnaire survey methodologies have often been used to analyze the causes of marine accidents. One of the disadvantages of these two methods is that they can only interpret the specific causes of one particular marine accident at a time. They cannot analyze and find the common causes of most marine accidents. Therefore, this study integrates the Automatic Identification System, Geographic Information System, and an e-chart to explore the relationship between environmental factors (wind, wave, tide, and current), locations, and significant common causes of marine accidents. Firstly, an Automatic Identification System is used to collect the traffic flows of vessels entering/exiting the port. The locations of maritime accidents were then plotted on an e-chart, after which we can quickly analyze the locations of marine accidents on the e-chart. Furthermore, environmental data are displayed using Geographic Information System. Subsequently, all data, including traffic flows of vessels, locations of marine accidents, and environmental data, are integrated into the e-chart simultaneously. As a result, the information related to factors affecting the probability of marine accidents could be displayed clearly on the e-chart. Finally, findings and conclusions are given to port authorities to help manage the ship traffic flow and reduce the probability of the occurrence of marine accidents around the port efficiently.

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

Optimization of Algicidal Activity for Alteromonas sp. FDHY-03 against Harmful Dinoflagellate Prorocentrum donghaiense - Qianqian Wang; Xinguo Shi; Yisong Guo; Pin Lv; Yuying Zhong; Hui Xie; Jianfeng Chen (Journal of Marine Science and Engineering, 2022)
Prorocentrum donghaiense is a harmful-algal-bloom-forming species of planktonic dinoflagellates widely distributed around the world, which threatens the marine environment and human health. Bacteria are promising biological agents to control algal growth in HABs. Previously, we isolated an Alteromonas sp. FDHY-03, a P. donghaiense-lysing bacteria strain, from Xiapu Sea area of China. In order to improve the algicidal activity of this strain, we optimized the medium composition and culture conditions. Based on single-factor method experiment design, the optimum medium component of algicidal effect for strain FDHY-03 was sucrose and peptone. The result of Plackett–Burman design indicated that three significant factors (sucrose, peptone, and rotational speed) appeared. Finally, the concentrations of key factors were confirmed by central composite design (CCD) and response surface methodology (RSM). Under the optimized medium, the algicidal rate of strain FDHY-03 against P. donghaiense improved by 67.15%, and the OD600 value increased by 2.86-fold. The optimal source and condition were sucrose 0.46% (w/v), peptone 4.25% (w/v) addition, and rotation speed 255 rpm. Overall, this study provides an optimized method and optimum medium for improving the algicidal activity against P. donghaiense, and has a positive influence on algae-lysing bacteria for controlling the blooms of the algae in the environment.

Bioactivity-guided isolation of compounds from Sophora flavescens with antibacterial activity against Acinetobacter baumannii - Pin Li; Wern Chern Chai; Zhan-Yi Wang; Kai-Jun Tang; Jin-Yao Chen; Henrietta Venter; Susan J. Semple; Lan Xiang (Natural Product Research, 2022)

Effects of perfluorooctanoic acid (PFOA) on activated sludge microbial community under aerobic and anaerobic conditions - Duanyi Huang; Rui Xu; Xiaoxu Sun; Yongbin Li; Enzong Xiao; Zhimin Xu; Qi Wang; Pin Gao; Zhaohui Yang; Hanzhi Lin; Weimin Sun (Environmental Science and Pollution Research, 2022)

Effect of gradation variation on particle transport process in a generalized flash flood gully via CFD-DEM method - Yi-pin Nie; Ling Lan; Xu-feng Yan; Xie-kang Wang (Acta Geophysica, 2022)

Keystone taxa and functional analysis in arsenic and antimony co-contaminated rice terraces - Pingzhou Su; Pin Gao; Weimin Sun; Wenlong Gao; Fuqing Xu; Qi Wang; Enzong Xiao; Mohsen Soleimani; Xiaoxu Sun (Environmental Science and Pollution Research, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Correction to: Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Paleolimnological evidence for lacustrine environmental evolution and paleo-typhoon records during the late Holocene in eastern Taiwan - Liang-Chi Wang; Yu-Min Chou; Huei-Fen Chen; Yuan-Pin Chang; Hong-Wei Chiang; Tien-Nan Yang; Liang-Jian Shiau; Yue-Gau Chen (Journal of Paleolimnology, 2022)

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

An Energy-Saving Position Control Strategy for Deep-Sea Valve-Controlled Hydraulic Cylinder Systems - Jia-Bin Wu; Li Li; Yong-Kang Yan; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly utilized in the underwater manipulator, which is the most important tool for subsea tasks. Hydraulic oil viscosity is very sensitive to pressure. Therefore, when working at different depths under different ambient pressures in the sea, the hydraulic oil viscosity and the pipeline pressure loss in the deep-sea VCHCS vary greatly, which seriously affects the energy efficiency of the system. In addition, the control accuracy of the deep-sea VCHCS is also influenced by changes in the hydraulic oil viscosity and the pipeline pressure loss. In order to realize energy-saving control, this research introduces a proportional relief valve and develops a variable pump pressure control strategy. At the same time, a variable gain proportional-integral-derivative (PID) algorithm is designed to achieve precise control. A co-simulation model of the deep-sea VCHCS is then established, and many simulation analyses are carried out. Compared with traditional PID control with a constant pump pressure, the proposed method presents advantages such as lower energy consumption, better control accuracy, better resistance to load impact, and accuracy consistency under different working depths. Among them, when working at 11 km depth in the sea, the proposed method is capable of saving energy by 36.5% for the multi-step movement, by 30% for the harmonic movement, and by 47% for the complex movement. The present work in this research provides a solution that can realize energy saving and precise control of the deep-sea VCHCS at the same time in the wide span of depth in the sea.

Short Review on Advances in Hydrogel-Based Drug Delivery Strategies for Cancer Immunotherapy - Hee Seung Seo; Chi-Pin James Wang; Wooram Park; Chun Gwon Park (Tissue Engineering and Regenerative Medicine, 2022)

Working Performance of the Deep-Sea Valve-Controlled Hydraulic Cylinder System under Pressure-Dependent Viscosity Change and Hydrodynamic Effects - Jia-Bin Wu; Li Li; Xing-Long Zou; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly used for actuators such as manipulators in deep-sea equipment, whose working performance is crucial to subsea tasks. Affected by the ambient pressure introduced by the pressure compensator, the viscosity of the hydraulic oil increases significantly. On this basis, the viscosity changes further when flowing in the slender pipeline, making the pipeline pressure loss substantially increase and subsequently affecting the working performance of the deep-sea VCHCS. Aiming at this issue, a detailed nonlinear mathematical model of the deep-sea VCHCS is established, in which the viscosity-pressure characteristics of the hydraulic oil is considered to take the viscosity changes in the pipeline into account. Besides, the hydrodynamic effects are also included in the model. Then the corresponding numerical simulation model of the deep-sea VCHCS is established, and its working performance at different depths is simulated and analyzed. When the depth is 11km, the extension and retraction movements are delayed by 52.50% and 43.12% respectively. The root cause of the delay is then analyzed and discussed. Finally, the parameters that affect the working performance are studied, and suggestions to reduce or eliminate the delay phenomenon are given. The results can provide theoretical support for the performance optimization of the deep-sea VCHCS.

Educating Primary Care Providers and Associate Care Providers About Hepatitis C Screening of Baby Boomers: a Multi-practice Study - Bertha E. Flores; Andrea A. Fernandez; Chen-Pin Wang; Raudel Bobadilla; Ludivina Hernandez; Mamta K. Jain; Barbara J. Turner (Journal of Cancer Education, 2022)

Refractory systemic capillary leak syndrome treated with bevacizumab: a case report - Pin Wang; Chien-Hui Chan; Hsuan-Fei Chen; Woei-Yau Kao; Tzu-Rong Peng (Angiogenesis, 2022)

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Citric acid and AMF inoculation combination–assisted phytoextraction of vanadium (V) by Medicago sativa in V mining contaminated soil - Lang Qiu; Wenlong Gao; Zhigang Wang; Baoqin Li; Weimin Sun; Pin Gao; Xiaoxu Sun; Benru Song; Yanxu Zhang; Tianle Kong; Hanzhi Lin (Environmental Science and Pollution Research, 2021)

Stochastic Modelling of Respiratory System Elastance for Mechanically Ventilated Respiratory Failure Patients - Jay Wing Wai Lee; Yeong Shiong Chiew; Xin Wang; Chee Pin Tan; Mohd Basri Mat Nor; Nor Salwa Damanhuri; J. Geoffrey Chase (Annals of Biomedical Engineering, 2021)

Magnetic porous biochar as a renewable and highly effective adsorbent for the removal of tetracycline hydrochloride in water - Hucheng Yang; Hao Yu; Jiahao Wang; Tao Ning; Pin Chen; Jing Yu; Siyuan Di; Shukui Zhu (Environmental Science and Pollution Research, 2021)

Five polyketides isolated from the marine-derived fungus Arthrinium Sp. - Zhaihai Zhao; Wanjing Ding; Pin-Mei Wang; Daoqiong Zheng; Jinzhong Xu (Natural Product Research, 2021)

SAA1 regulates pro-labour mediators in term labour by activating YAP pathway - Yanmin Jiang; Li Pin; Weiqun Shi; Qian Huang; Lele Wang; Huishu Liu (Molecular and Cellular Biochemistry, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

Cerebral Small Vessel Disease Influences Hippocampal Subfield Atrophy in Mild Cognitive Impairment - Fennie Choy Chin Wong; Chathuri Yatawara; Audrey Low; Heidi Foo; Benjamin Yi Xin Wong; Levinia Lim; Brian Wang; Dilip Kumar; Kok Pin Ng; Nagaendran Kandiah (Translational Stroke Research, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Deep convolutional neural network–based pixel-wise landslide inventory mapping - Zhaoyu Su; Jun Kang Chow; Pin Siang Tan; Jimmy Wu; Ying Kit Ho; Yu-Hsing Wang (Landslides, 2021)

Eliminating vascular interference from the Spot Sign contributes to predicting hematoma expansion in individuals with spontaneous cerebral hemorrhages - Pan Yi; Min Xu; Pin Chen; Yu Luo; Dongdong Wang; Hui Wang; Cunzu Wang (Acta Neurologica Belgica, 2021)

First Detection and Molecular Identification of Entamoeba in Yaks from China - Mei Ren; Fan Yang; Jing-min Gou; Pin-xue Wang; Min Zou; Xiao-hong Zhong; Qing Lin (Acta Parasitologica, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

MicroRNA-143–5p modulates pulmonary artery smooth muscle cells functions in hypoxic pulmonary hypertension through targeting HIF-1α - Bi Tang; Ming-ming Tang; Qing-mei Xu; Jian-lu Guo; Ling Xuan; Jing zhou; Xiao-jing Wang; Heng Zhang; Pin-fang Kang (Journal of Biosciences, 2020)

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

Flavobacterium ajazii sp. nov., Isolated from Seaweed of Gouqi Island, China - Ishrat Khan; Sanjit Chandra Debnath; Cen Yan; Can Chen; Yan Xu; Wen-Jie Wang; Yu-Chao Yu; Dao-Qiong Zheng; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2020)

Pathogenic characterization of Aeromonas salmonicida subsp. masoucida turbot isolate from China - Ping Wang; Jie Li; Tian Tian He; Nan Li; Zhao Lan Mo; Pin Nie; Hai Xia Xie (Journal of Fish Diseases, 2020)
Aeromonas salmonicida is a gram‐negative bacterium that is the causative agent of furunculosis. An A. salmonicida strain was isolated from diseased turbot ( Scophthalmus maximus ) with the sign of furunculosis from North China. Based on vapA gene, the strain was further classified as A. salmonicida subsp. masoucida RZ6S‐1. Culturing RZ6S‐1 strain at high temperature (28°C) obtained the virulence attenuated strain RZ6S. Genome sequence comparison between the two strains revealed the loss of the type IV secretion system (T4SS) and type III secretion system (T3SS) from the native plasmid pAsmB‐1 and pAsmC‐1 of wild‐type strain RZ6S‐1, respectively. Further study demonstrated that the wild‐type strain RZ6S‐1, but not its derivative mutant RZ6S, can stimulate apoptosis. Elevated protein level of cleaved caspase‐3 was detected from epithelioma papulosum cyprinid (EPC) cells infected with wild‐type strain RZ6S‐1 as compared with that infected with RZ6S strain. Meanwhile, the invasion of the mutant strain RZ6S was about 17‐fold higher than the wild‐type strain RZ6S‐1, suggesting that some protein(s) from A. salmonicida subsp. masoucida RZ6S‐1 suppress its invasion. The RZ6S mutant strain was attenuated, since its LD 50 is over 10,000 times higher compared to the wild‐type strain as revealed in the turbot infection model.

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Transnasal endoscopic treatment on a rare case of intracranial penetrating brain injury - Min Xu; Yu Luo; Pin Chen; Pan Yi; Cun-zu Wang (Acta Neurologica Belgica, 2020)

Altered Mineral Metabolism and Disequilibrium Between Calcification Promoters and Inhibitors in Chronic Hemodialysis Patients - Chia-Liang Wang; Kuan-Pin Lin; Guoo-Shyng W. Hsu; Kai-Li Liu; Chih-Hung Guo (Biological Trace Element Research, 2020)

Correction to: Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Application of a stable carbon isotope for identifying Broussonetia papyrifera pollen - Chien-Cheng Jung; Chuan-Pin Lee; Wen-Chi Wang; Ming-Chee Wu; Huey-Jen Su (Environmental Science and Pollution Research, 2019)

Functional analysis of McSnRK1 (SNF1-related protein kinase 1) in regulating Na/K homeostasis in transgenic cultured cells and roots of halophyte Mesembryanthemum crystallinum - Hau-Hsuan Hwang; Chih-Hao Wang; Hsiao-Wei Huang; Chih-Pin Chiang; Shin-Fei Chi; Fan-Chen Huang; Hungchen E. Yen (Plant Cell Reports, 2019)

Effects of vermicomposting on the main chemical properties and bioavailability of Cd/Zn in pure sludge - Jizhou Zhang; Maral Erdene Sugir; Yunying Li; Lei Yuan; Meng Zhou; Pin Lv; Zhimin Yu; Limin Wang; Dongxing Zhou (Environmental Science and Pollution Research, 2019)

Zircon trace elements and magma fertility: insights from porphyry (-skarn) Mo deposits in NE China - Qihai Shu; Zhaoshan Chang; Yong Lai; Xinlu Hu; Huaying Wu; Yong Zhang; Pin Wang; Degao Zhai; Cheng Zhang (Mineralium Deposita, 2019)

Changes in the spatial pattern of rice exposure to heat stress in China over recent decades - Pin Wang; Tangao Hu; Feng Kong; Dengrong Zhang (Climatic Change, 2019)

Dynamic Properties of Thermally Treated Granite Subjected to Cyclic Impact Loading - Pin Wang; Tubing Yin; Xibing Li; Shuaishuai Zhang; Lv Bai (Rock Mechanics and Rock Engineering, 2019)

The application of forward osmosis for simulated surface water treatment by using trisodium citrate as draw solute - Shihui Yang; Baoyu Gao; Pin Zhao; Chen Wang; Xue Shen; Qinyan Yue; Ho kyong Shon (Environmental Science and Pollution Research, 2019)

Flavobacterium sharifuzzamanii sp. nov., Isolated from the Sediments of the East China Sea - Sanjit C. Debnath; Can Chen; Shu-Xia Liu; Ya-Nan Di; Dao-Qiong Zheng; Xin-Yang Li; Xue-Wei Xu; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2019)

Science as a Bridge in Communicating Needs and Implementing Changes towards Wetland Conservation in Taiwan - Hsiao-Wen Wang; Adrienne Dodd; Pin-Han Kuo; Ben LePage (Wetlands, 2018)

Analysis of Dynamic Fracture Compliance Based on Poroelastic Theory. Part II: Results of Numerical and Experimental Tests - Ding Wang; Pin-bo Ding; Jing Ba (Pure and Applied Geophysics, 2018)

Water Management to Enhance Ecosystem Services in a Coastal Wetland in Taiwan - Pin‐Han Kuo; Hsiao‐Wen Wang (Irrigation and Drainage, 2018)
Wetlands provide multiple ecosystem services, and wetland hydrology is one of the key determinants of wetland function. Budai Salt Pan Wetland provides at least 11 ecosystem services, i.e. food provision, genetic materials, climate regulation, water purification and treatment, natural hazard regulation, pollination, spiritual and inspirational, recreational, aesthetic, educational and nutrient cycling. As the wetland is completely encompassed by dikes, there is no natural hydrological connectivity, and the wetland frequently dries out during the dry season due to lack of management and insufficient rainfall. In order to enhance wetland function, including habitat quality and ecosystem services, this study created a water management plan which mimics nature through water gate operation. We conducted experimental gate operations and evaluated the potential impacts on ecosystem services. The results show a positive impact on two of the ecosystem services, climate regulation and genetic materials, due to the increased moisture content and feeding bird individuals after gate operation. There was an insignificant change in the natural hazard regulation service as the gate operation tested in this study addressed issues of water supply rather than increasing detention space through draining. Through mimicking nature, sustainable water management techniques have the potential to enhance ecosystem services in wetlands. Copyright © 2018 John Wiley & Sons, Ltd.

Analyzing gravity anomaly variations before the 2016 Ms 6.4 earthquake in Menyuan, Qinghai with an interpolation/cutting potential field separation technique - Jin-Zhao Liu; Tong-Qing Wang; Zhao-Hui Chen; Pin Zhang; Chuan-Dong Zhu; Shuang-Xi Zhang (Applied Geophysics, 2018)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Rice yield development and the shrinking yield gaps in China, 1981–2008 - Yi Chen; Pin Wang; Zhao Zhang; Fulu Tao; Xing Wei (Regional Environmental Change, 2017)

Future extreme temperature and its impact on rice yield in China - Zhao Zhang; Yi Chen; Chenzhi Wang; Pin Wang; Fulu Tao (International Journal of Climatology, 2017)
Rice in China is increasingly suffered from extreme temperature stress ( ETS ) with ongoing climate change. It is projected that ETS would increase notably across the world in the future. However, the spatio‐temporal change of ETS in main rice planting areas in China is still unclear; and the future yield loss caused by ETS ( YL ETS ) has seldom been investigated quantitatively. In this study, we first investigated the spatio‐temporal change of ETS across China under 20 climate change scenarios consisting of five global climate models and four Representative Carbon Pathways (2.6, 4.5, 6.0, and 8.5). Then, using a process‐based crop model ( MCWLA ‐Rice), its 30 sets of model parameters and the 20 climate change scenarios, we conducted a super‐ensemble assessment to investigate the YL ETS over 2020–2049, relative to the baseline period (1980–2009), across China. The results showed that, an increased heat ETS and a decreased cold ETS would be expected for most areas. As a result, a large spatial variability of yield loss would be expected in the future, including severely cold stress for region I (northeastern China, single rice) and region IV (southern China, early rice), but severely heat stress for region III (the middle and lower reaches of Yangtze River, single rice) and region IV (southern China, late rice). Comparing yield loss from both ETS , a decreased change in yield loss would be mainly expected in region I (northeastern China, single rice), while an increased change for region III (the middle and lower reaches of Yangtze River, single rice) and IV (southern China, late rice), with less change for region II (southwestern China, single rice) and IV (southern China, early rice). Finally, some adaptation measures were proposed for the ETS ‐sensitive areas. Our findings are useful to develop effective policies to cope with climate risk and relieve ETS disasters.

Characterization of OATP1B3 and OATP2B1 transporter expression in the islet of the adult human pancreas - Michelle Kim; Perri Deacon; Rommel G. Tirona; Richard B. Kim; Christopher L. Pin; Henriette E. Meyer zu Schwabedissen; Rennian Wang; Ute I. Schwarz (Histochemistry and Cell Biology, 2017)

Nonlinear biotic ligand model for assessing alleviation effects of Ca, Mg, and K on Cd toxicity to soybean roots - Bo-Ching Chen; Pin-Jie Wang; Pei-Chi Ho; Kai-Wei Juang (Ecotoxicology, 2017)

Seasonal modeling of hand, foot, and mouth disease as a function of meteorological variations in Chongqing, China - Pin Wang; Han Zhao; Fangxin You; Hailong Zhou; William B. Goggins (International Journal of Biometeorology, 2017)

Three-dimensional tomography using high-power induced polarization with the similar central gradient array - Jun-Lu Wang; Pin-Rong Lin; Meng Wang; Dang Li; Jian-Hua Li (Applied Geophysics, 2017)

Autonomous cyanobacterial harmful algal blooms monitoring using multirotor UAS - Pin Lyu; Yasir Malang; Hugh H.T. Liu; Jizhou Lai; Jianye Liu; Bin Jiang; Mingzhi Qu; Stephen Anderson; Daniel D. Lefebvre; Yuxiang Wang (International Journal of Remote Sensing, 2017)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

The death of the circulatory system diseases in China: provincial socioeconomic and environmental perspective - Haixia Pu; Jiatian Li; Pin Wang; Linlin Cui; Huaxin Wang (Environmental Science and Pollution Research, 2017)

Spatial variation of air quality index and urban driving factors linkages: evidence from Chinese cities - Haixia Pu; Kunli Luo; Pin Wang; Shaobin Wang; Shun Kang (Environmental Science and Pollution Research, 2017)

Recent patterns of production for the main cereal grains: implications for food security in China - Xing Wei; Zhao Zhang; Pin Wang; Fulu Tao (Regional Environmental Change, 2017)

Contribution of redox-dependent activation of endothelial Nlrp3 inflammasomes to hyperglycemia-induced endothelial dysfunction - Yang Chen; Lei Wang; Ashley L. Pitzer; Xiang Li; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2016)

Erratum to: The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

Determination of Dynamic Flexural Tensile Strength of Thermally Treated Laurentian Granite Using Semi-Circular Specimens - Tubing Yin; Pin Wang; Xibing Li; Bangbiao Wu; Ming Tao; Ronghua Shu (Rock Mechanics and Rock Engineering, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

A sudden cardiac asystole and cardiopulmonary resuscitation of trigeminocardiac reflex during retrosigmoid approach surgery - Xu Min; Bo Jixiang; Chen Pin; Wang Cunzu (Acta Neurologica Belgica, 2016)

Imaging Rainfall Infiltration Processes with the Time-Lapse Electrical Resistivity Imaging Method - Gang Zhang; Gui-Bin Zhang; Chien-chih Chen; Ping-Yu Chang; Tzu-Pin Wang; Horng-Yuan Yen; Jia-Jyun Dong; Chuen-Fa Ni; Su-Chin Chen; Chao-Wei Chen; Zheng-yuan Jia (Pure and Applied Geophysics, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Molecular characterization and expression of ZAP-70 in Nile tilapia (Oreochromis niloticus) in response to Streptococcus agalactiae stimulus - Zhen Gan; Bei Wang; Wei Zhou; Yishan Lu; Yanfei Zhang; JiChang Jian; Zaohe Wu; Pin Nie (Genes & Genomics, 2016)

Deep-Water Sedimentary Characteristics and Response in the Reed Area of the Southern South China Sea - Zheng Hong-Bo; Yan Pin; Yan-Lin Wang; Yu-Qing Xing (Marine Georesources & Geotechnology, 2016)

How much yield loss has been caused by extreme temperature stress to the irrigated rice production in China? - Pin Wang; Zhao Zhang; Yi Chen; Xing Wei; Boyan Feng; Fulu Tao (Climatic Change, 2016)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

A rare self-injurious case of multiple penetrating brain injury by nails in a young patient with depressive disorder - Min Xu; Jinkun Wen; Xun Zhu; Pin Chen; Cunzu Wang (Acta Neurologica Belgica, 2015)

Subgroups of US IRAQ and Afghanistan veterans: associations with traumatic brain injury and mental health conditions - Carlos A. Jaramillo; Douglas B. Cooper; Chen-Pin Wang; David F. Tate; Blessen C. Eapen; Gerald E. York; Mary Jo Pugh (Brain Imaging and Behavior, 2015)

Ontogenetic development of adipose tissue in grass carp (Ctenopharyngodon idellus) - Pin Liu; Hong Ji; Chao Li; Jingjing Tian; Yifei Wang; Ping Yu (Fish Physiology and Biochemistry, 2015)

CARD9 Deficiencies Linked to Impaired Neutrophil Functions Against Phialophora verrucosa - Pin Liang; Xiaowen Wang; Runchao Wang; Zhe Wan; Wenling Han; Ruoyu Li (Mycopathologia, 2015)

Dynamic variability of the heading–flowering stages of single rice in China based on field observations and NDVI estimations - Zhao Zhang; Xiao Song; Yi Chen; Pin Wang; Xing Wei; Fulu Tao (International Journal of Biometeorology, 2015)

EGFR mediates docetaxel resistance in human castration-resistant prostate cancer through the Akt-dependent expression of ABCB1 (MDR1) - Tzyh-Chyuan Hour; Shiu-Dong Chung; Wang-Yi Kang; Ying-Chu Lin; Shu-Ju Chuang; A-Mei Huang; Wen-Jeng Wu; Shu-Pin Huang; Chao-Yuan Huang; Yeong-Shiau Pu (Archives of Toxicology, 2015)

The spatio-temporal variations of surface water quality in China during the “Eleventh Five-Year Plan” - Jingbo Sun; Yi Chen; Zhao Zhang; Pin Wang; Xiao Song; Xing Wei; Boyan Feng (Environmental Monitoring and Assessment, 2015)

The versatile roles of CARDs in regulating apoptosis, inflammation, and NF-κB signaling - Wen-Pin Kao; Chao-Yu Yang; Tsung-Wei Su; Yin-Ting Wang; Yu-Chih Lo; Su-Chang Lin (Apoptosis, 2015)

A novel SMAD family protein, SMAD9 is involved in follicular initiation and changes egg yield of geese via synonymous mutations in exon1 and intron2 - Jun Xu; Jun Li; Haosen Wang; Guanglin Wang; Jie Chen; Pin Huang; Jienan Cheng; Lu Gan; Zhao Wang; Yafei Cai (Molecular Biology Reports, 2015)

Transplantation of mesenchymal stem cells into the renal medulla attenuated salt-sensitive hypertension in Dahl S rat - Junping Hu; Qing Zhu; Min Xia; Tai L. Guo; Zhengchao Wang; Pin-Lan Li; Wei-Qing Han; Fan Yi; Ningjun Li (Journal of Molecular Medicine, 2014)

Loss of EphB6 protein expression in human colorectal cancer correlates with poor prognosis - Libo Peng; Pin Tu; Xuan Wang; Shanshan Shi; Xiaojun Zhou; Jiandong Wang (Journal of Molecular Histology, 2014)

The complete mitochondrial genome of the brown leg mite, Aleuroglyphus ovatus (Acari: Sarcoptiformes): evaluation of largest non-coding region and unique tRNAs - En-Tao Sun; Chao-Pin Li; Liu-Wang Nie; Yu-Xin Jiang (Experimental and Applied Acarology, 2014)

Predictive value of circulating miR-328 and miR-134 for acute myocardial infarction - Fucheng He; Pin Lv; Xue Zhao; Xi Wang; Xuehan Ma; Weiwei Meng; Xianchun Meng; Shuling Dong (Molecular and Cellular Biochemistry, 2014)

Temperature variations and rice yields in China: historical contributions and future trends - Pin Wang; Zhao Zhang; Xiao Song; Yi Chen; Xing Wei; Peijun Shi; Fulu Tao (Climatic Change, 2014)

Spatial pattern and decadal change of agro-meteorological disasters in the main wheat production area of China during 1991–2009 - Zhao Zhang; Pin Wang; Yi Chen; Shuai Zhang; Fulu Tao; Xiaofei Liu (Journal of Geographical Sciences, 2014)

An EGFR gene of the Pacific oyster Crassostrea gigas functions in wound healing and promotes cell proliferation - Lingling Sun; Pin Huan; Hongxia Wang; Fengsong Liu; Baozhong Liu (Molecular Biology Reports, 2014)

Spatial and temporal changes of agro-meteorological disasters affecting maize production in China since 1990 - Zhao Zhang; Yi Chen; Pin Wang; Shuai Zhang; Fulu Tao; Xiaofei Liu (Natural Hazards, 2014)

Nod-Like Receptor Protein 1 Inflammasome Mediates Neuron Injury under High Glucose - Xian-Fang Meng; Xiao-Lan Wang; Xiu-Juan Tian; Zhi-Hua Yang; Guang-Pin Chu; Jing Zhang; Man Li; Jing Shi; Chun Zhang (Molecular Neurobiology, 2014)

Fluid inclusion and H–O–C isotope geochemistry of the Yaochong porphyry Mo deposit in Dabie Shan, China: a case study of porphyry systems in continental collision orogens - Pin Wang; Yan-Jing Chen; Bin Fu; Yong-Fei Yang; Mei Mi; Zhong-Lie Li (International Journal of Earth Sciences, 2014)

The heat deficit index depicts the responses of rice yield to climate change in the northeastern three provinces of China - Zhao Zhang; Xiaofei Liu; Pin Wang; Jiabing Shuai; Yi Chen; Xiao Song; Fulu Tao (Regional Environmental Change, 2014)

Spatiotemporal changes of global extreme temperature events (ETEs) since 1981 and the meteorological causes - Xiao Song; Zhao Zhang; Yi Chen; Pin Wang; Ming Xiang; Peijun Shi; Fulu Tao (Natural Hazards, 2014)

A study of earthquake inter-occurrence times distribution models in Taiwan - Chi-Hsuan Chen; Jui-Pin Wang; Yih-Min Wu; Chung-Han Chan; Chien-Hsin Chang (Natural Hazards, 2013)

APPLICATION OF A DECISION SUPPORT SYSTEM TO SUSTAINABLE LOWLAND PLANNING AND MANAGEMENT IN YUNLIN AREA, TAIWAN - Hsiao‐Wen Wang; Chun‐Yao Yang; Pin‐Han Kuo (Irrigation and Drainage, 2013)
Sustainable approaches are recognized as a necessity for lowland planning and management. The spatial dimension of sustainability engages relations between different land uses, ecosystems, and human effects at different scales and over time. Yunlin County, located in south‐western Taiwan, has abundant natural resources but has been suffering from flooding and land subsidence for a long time. With the effects of climate change, lowland management in this area is becoming complicated. Possible strategies should thus be considered and conveyed to decision‐makers in the most efficient and transparent way, so as to redirect further discussion towards the conflicting aspects. The study evaluated the possible consequences of three planning scenarios on safety, economic, and ecological resources as a whole based on the future developing trend. The scenarios were then compared by applying OSIRIS, a decision and evaluation support system, to highlight the conflicting sites and to propose an optimal strategy. The results illustrated that the current lowland management policy is not effective and sustainable. Instead, the Coastal Conservation Green Way scenario might not only ease flood threat but also provide ecological benefit. The study could thus contribute to enhanced communication between stakeholders and help achieve sustainable lowland management. Copyright © 2013 John Wiley & Sons, Ltd.

Assessment of climate change impacts on flooding vulnerability for lowland management in southwestern Taiwan - Hsiao-Wen Wang; Pin-Han Kuo; Jenq-Tzong Shiau (Natural Hazards, 2013)

The use of allelic imbalance to ascertain cis-regulation for human UGT2B7 in vivo - Pin-Yi Wang; Dezheng Huo; Chang Sun; Olufunmilayo I. Olopade (European Journal of Clinical Pharmacology, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Assessment of seismic hazard associated with the Meishan fault in Central Taiwan - Jui-Pin Wang; Duruo Huang; Su-Chin Chang (Bulletin of Engineering Geology and the Environment, 2013)

Increasing concentrations of aerosols offset the benefits of climate warming on rice yields during 1980–2008 in Jiangsu Province, China - Jiabing Shuai; Zhao Zhang; Xiaofei Liu; Yi Chen; Pin Wang; Peijun Shi (Regional Environmental Change, 2013)

Fibroblast growth factor (Fgf) signaling pathway regulates liver homeostasis in zebrafish - Su-Mei Tsai; Da-Wei Liu; Wen-Pin Wang (Transgenic Research, 2013)

Cordyceps sinensis protects against renal ischemia/reperfusion injury in rats - Hua-Pin Wang; Ching-Wen Liu; Hsueh-Wen Chang; Jen-Wei Tsai; Ya-Zhu Sung; Li-Ching Chang (Molecular Biology Reports, 2013)

Impact of chilling injury and global warming on rice yield in Heilongjiang Province - Xiaofei Liu; Zhao Zhang; Jiabing Shuai; Pin Wang; Wenjiao Shi; Fulu Tao; Yi Chen (Journal of Geographical Sciences, 2013)

Reconstruction of oceanographic changes based on diatom records of the core MD012380 since Marine Isotopic Stage 11 in the Banda Sea - Yuan‐Pin Chang; Chung‐Ching Liao; Wei‐Lung Wang (Journal of Quaternary Science, 2012)
Current surface production in the Banda Sea is primarily controlled by monsoonal forcing, the strength of the Indonesian throughflow and surface salinity, and is sensitive to global climate changes. Therefore, variations of paleoproductivity represented by the abundance of diatoms are estimated to assist in understanding possible hydrological changes during glacial–interglacial cycles since Marine Isotopic Stage 11 (MIS 11). During the interglacials, the enhanced austral winter monsoon (southeast monsoon) encourages deepening of the mixed layer and uplifting of the thermocline, thereby increasing surface production. However, accompanied enhancement of the Indonesian throughflow (ITF) within the interglacials brings warm and less‐saline water from the central part of the warm pool water entering the Banda Sea to mitigate development of the upwelling system. Conversely, cooling of the Northern Hemisphere forces the strengthening of the austral summer monsoon (northwest monsoon) to depress the upwelling and reduce production during glacial intervals, whereas the weakening flow of the ITF reduces the influence of low‐salinity capping effects and benefits production. Higher abundance of Chaetoceros sp., dominant in upwelling environments, observed in glacials suggests that strength of the ITF is the most important factor in controlling the vertical thermostructure of the Banda Sea. Copyright © 2012 John Wiley & Sons, Ltd.

PGA distributions and seismic hazard evaluations in three cities in Taiwan - Jui-Pin Wang; Su-Chin Chang; Yih-Min Wu; Yun Xu (Natural Hazards, 2012)

Identification of Putative Artemisia annua ABCG Transporter Unigenes Related to Artemisinin Yield Following Expression Analysis in Different Plant Tissues and in Response to Methyl Jasmonate and Abscisic Acid Treatments - Ling Zhang; Xu Lu; Qian Shen; Yunfei Chen; Tao Wang; Fangyuan Zhang; Shaoyan Wu; Weimin Jiang; Pin Liu; Lida Zhang; Yueyue Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2012)

Increased susceptibility of algal symbionts to photo-inhibition resulting from the perturbation of coral gastrodermal membrane trafficking - Chii-Shiarng Chen; Shih-Pin Yeh; Li-Hsueh Wang; Hsing-Hui Li; Uang Wan-Nan Chen (Science China Life Sciences, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Transcriptomic Analysis of the Clam Meretrix meretrix on Different Larval Stages - Pin Huan; Hongxia Wang; Baozhong Liu (Marine Biotechnology, 2012)

Lymphocyte α-kinase is a gout-susceptible gene involved in monosodium urate monohydrate-induced inflammatory responses - Shu-Jung Wang; Hung-Pin Tu; Albert Min-Shan Ko; Shang-Lun Chiang; Shean-Jaw Chiou; Su-Shin Lee; Yi-Shan Tsai; Chi-Pin Lee; Ying-Chin Ko (Journal of Molecular Medicine, 2011)

APPLICATION OF LANDSCAPE ECOLOGICAL DECISION AND EVALUATION SUPPORT SYSTEM ON FLOOD MITIGATION STRATEGIES - Chun‐Yao Yang; Hsiao‐Wen Wang; Pin‐Han Kuo (Irrigation and Drainage, 2011)
While flood mitigation measures are needed in flood‐prone areas, some may impact the environment, for example by causing habitat fragmentation. As flooding issues nowadays are more complicated and should be discussed taking multidisciplinary considerations into account, the purpose of this study was to evaluate the effects of land use changes on flooding, landscape pattern, and ecological resources as a whole, based on past environmental changes and trends in future development, using the concept of the Landscape Ecological Decision and Evaluation Support System Model (LEDESS). Yunlin County, one of the demonstration sites of the Regulation Project of Flood‐Prone Areas, proposed by the Water Resource Agency of Taiwan in 2005, was studied. We designed three scenarios, i.e. Scenario A for the current situation, Scenario B for the government policy, and Scenario C as a sustainable policy integrating room for water. We used people, planet, and profit as the indicators to understand the consequences under different scenarios. The results indicated that lots of land will be abandonedin the near future due to flooding regardless of whether or not mitigation measures are adopted. That is to say, the coastal area will turn into a wetland area through natural processes. Hence, we need to reconsider land use strategy. Copyright © 2011 John Wiley & Sons, Ltd.

Monitoring and estimating scale-dependent hierarchical relationships between Sicyopterus japonicus density and stream habitat features in different seasons in northern Taiwan - Hsiao-Hsuan Yu; Yu-Pin Lin; Cheng-Long Wang (Environmental Monitoring and Assessment, 2011)

Down-Regulation of Tumor-Associated NADH Oxidase, tNOX (ENOX2), Enhances Capsaicin-Induced Inhibition of Gastric Cancer Cell Growth - His-Ming Wang; Show-Mei Chuang; Yu-Ching Su; Yi-Hui Li; Pin Ju Chueh (Cell Biochemistry and Biophysics, 2011)

The distribution of annual maximum earthquake magnitude around Taiwan and its application in the estimation of catastrophic earthquake recurrence probability - Jui-Pin Wang; Chung-Han Chan; Yih-Min Wu (Natural Hazards, 2011)

Association of hypomethylation of LINE-1 repetitive element in blood leukocyte DNA with an increased risk of hepatocellular carcinoma - Jian-zhong Di; Xiao-dong Han; Wen-ye Gu; Yu Wang; Qi Zheng; Pin Zhang; Hui-min Wu; Zhong-zheng Zhu (Journal of Zhejiang University-SCIENCE B, 2011)

Estimation of nested spatial patterns and seasonal variation in the longitudinal distribution of Sicyopterus japonicus in the Datuan Stream, Taiwan by using geostatistical methods - Yu-Pin Lin; Cheng-Long Wang; Chi-Ru Chang; Hsiao-Hsuan Yu (Environmental Monitoring and Assessment, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

Typhoon Disturbance and Forest Dynamics: Lessons from a Northwest Pacific Subtropical Forest - Teng-Chiu Lin; Steven P. Hamburg; Kuo-Chuan Lin; Lih-Jih Wang; Chung-Te Chang; Yue-Joe Hsia; Matthew A. Vadeboncoeur; Cathy M. Mabry McMullen; Chiung-Pin Liu (Ecosystems, 2011)

Anticancer activity of a cyclooxygenase inhibitor, CX9051, in human prostate cancer cells: the roles of NF-κB and crosstalk between the extrinsic and intrinsic apoptotic pathways - Chiung-Hua Huang; Jih-Hwa Guh; Grace Shiahuy Chen; Pin-Hsuan Lu; Ji-Wang Chern (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Protection against HIV-envelope-induced neuronal cell destruction by HIV attachment inhibitors - Sharon Zhang; Louis Alexander; Tao Wang; Michele Agler; Nannon Zhou; Hua Fang; John Kadow; Paul Clapham; Pin-Fang Lin (Archives of Virology, 2010)

Construction and Characterization of a Bacterial Artificial Chromosome (BAC) Library of Pacific White Shrimp, Litopenaeus vannamei - Xiaojun Zhang; Yang Zhang; Chantel Scheuring; Hong-Bin Zhang; Pin Huan; Bing Wang; Chengzhang Liu; Fuhua Li; Bin Liu; Jianhai Xiang (Marine Biotechnology, 2010)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

The last 100 000 years' palaeoenvironmental changes inferred from the diatom assemblages of core MD012404 from the Okinawa Trough, East China Sea - Yuan‐Pin Chang; Wei‐Lung Wang; Min‐Te Chen (Journal of Quaternary Science, 2009)
The diatom assemblage records preserved in a sedimentary core MD012404 retrieved from the Okinawa Trough in the East China Sea (ECS) imply palaeoenvironmental changes of the last 100 ka. Our statistical analyses of diatom species abundance data indicate that the assemblages dominate open ocean and warm water, coastal water and freshwater masses in the ECS. These proxy species were used to infer the long‐term variation in surface hydrological conditions and palaeoclimate. Cycles of ca. 23 ka observed in the relative abundance of the tychopelagic species Paralia sulcata indicate that the increases in precipitation driven by solar insolation might have controlled the diatom assemblages in the ECS. The diatom records also indicate relatively low abundances of tropical, tychopelagic and freshwater species during millennial‐scale cold events such as the Younger Dryas and Heinrich events, which have been well expressed in the high‐latitude Northern Hemisphere climate. The floral patterns are interpreted as synchronous cooling and more saline sea surface conditions in the ECS caused by the enhanced Asian winter monsoon during the Northern Hemisphere cold events. The higher abundances of tropical species during deglaciation and the Holocene might have been linked to gradual increases in the inflow of the Kuroshio into the Okinawa Trough. The records also suggest a temporary reduction in tropical species from 5 to 3 ka, corresponding to the Pulleniatina Minimum Event during which the warm‐water planktic foraminifer Pulleniatina obliquiloculata was rare. Copyright © 2009 John Wiley & Sons, Ltd.

Cell Type-Specific Targeting with Surface-Engineered Lentiviral Vectors Co-displaying OKT3 Antibody and Fusogenic Molecule - Haiguang Yang; Kye-Il Joo; Leslie Ziegler; Pin Wang (Pharmaceutical Research, 2009)

Co-circulating genetically divergent A2 human metapneumovirus strains among children in southern Taiwan - Hsuan-Chen Wang; Sheng-Wen Huang; Shainn-Wei Wang; Huey-Pin Tsai; David Kiang; Shih-Min Wang; Ching-Chuan Liu; Ih-Jen Su; Jen-Ren Wang (Archives of Virology, 2008)

Molecular modeling of zinc and copper binding with Alzheimer’s amyloid β-peptide - Daxiong Han; Haiyan Wang; Pin Yang (BioMetals, 2008)

Geostatistical approaches and optimal additional sampling schemes for spatial patterns and future sampling of bird diversity - Yu‐Pin Lin; Ming‐Sheng Yeh; Dong‐Po Deng; Yung‐Chieh Wang (Global Ecology and Biogeography, 2008)
Aim To evaluate geostatistical approaches, namely kriging, co‐kriging and geostatistical simulation, and to develop an optimal sampling design for mapping the spatial patterns of bird diversity, estimating their spatial autocorrelations and selecting additional samples of bird diversity in a 2450 km 2 basin. Location Taiwan. Methods Kriging, co‐kriging and simulated annealing are applied to estimate and simulate the spatial patterns of bird diversity. In addition, kriging and co‐kriging with a genetic algorithm are used to optimally select further samples to improve the kriging and co‐kriging estimations. The association between bird diversity and elevation, and bird diversity and land cover, is analysed with estimated and simulated maps. Results The Simpson index correlates spatially with the normalized difference vegetation index (NDVI) within the micro‐scale and the macro‐scale in the study basin, but the Shannon diversity index only correlates spatially with NDVI within the micro‐scale. Co‐kriging and simulated annealing simulation accurately simulate the statistical and spatial patterns of bird diversity. The mean estimated diversity and the simulated diversity increase with elevation and decrease with increasing urbanization. The proposed optimal sampling approach selects 43 additional sampling sites with a high spatial estimation variance in bird diversity. Main conclusions Small‐scale variations dominate the total spatial variation of the observed diversity due to a lack of spatial information and insufficient sampling. However, simulations of bird diversity consistently capture the sampling statistics and spatial patterns of the observed bird diversity. The data thus accumulated can be used to understand the spatial patterns of bird diversity associated with different types of land cover and elevation, and to optimize sample selection. Co‐kriging combined with a genetic algorithm yields additional optimal sampling sites, which can be used to augment existing sampling points in future studies of bird diversity.

Selenium and GPx-1 overexpression protect mammalian cells against UV-induced DNA damage - Manjeshwar S. Baliga; Hengbing Wang; Pin Zhuo; Jeffrey L. Schwartz; Alan M. Diamond (Biological Trace Element Research, 2007)

Selenium and GPx-1 overexpression protect mammalian cells against UV-induced DNA damage - Manjeshwar S. Baliga; Hengbing Wang; Pin Zhuo; Jeffrey L. Schwartz; Alan M. Diamond (Biological Trace Element Research, 2007)

Immunohistochemical Detection of Apoptotic Proteins, p53/Bax and JNK/FasL Cascade, in the Lung of Rats Exposed to Cigarette Smoke - Cheng-Hsun Wu; Hui-Hsuan Lin; Fu-Pin Yan; Cheng-Hua Wu; Chau-Jong Wang (Archives of Toxicology, 2006)

Hydrogenation properties of mechanically milled Mg2Ni0.8Cr0.2-CoO/Al2O3 composites - Xiu-li Wang; Jiang-ping Tu; Chang-pin Chen; Xiao-bin Zhang; Xin-bing Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Water Chemistry and Temporal Variation of Nutrients in Stemflow of Three Dominant Tree Species in the Subtropics of the Fu-Shan Forest - Chiung-Pin Liu; Hen-Biau King; Ming-Kuang Wang; Yue-Joe Hsia; Jeen-Lian Hwong (Water, Air, & Soil Pollution, 2004)

Calcium-antagonizing activity of S -petasin, a hypotensive sesquiterpene from Petasites formosanus , on inotropic and chronotropic responses in isolated rat atria and cardiac myocytes - Guei-Jane Wang; Jyh-Fei Liao; Kadon K. Hintz; Chuen-Chao Shi; Chieh-Fu Chen; Wen-Pin Chen; Ming-Jai Su; Yun-Lian Lin; Jun Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Targeted suppression of the ferroxidase and iron trafficking activities of the multicopper oxidase Fet3p from Saccharomyces cerevisiae - Tzu-Pin Wang; Liliana Quintanar; Scott Severance; Edward I. Solomon; Daniel J. Kosman (JBIC Journal of Biological Inorganic Chemistry, 2003)

Study on business pollution and its countermeasures in Shanghai - Kai Yang; Yun Wang; Xiangnan Gan; Pin Gu (Chinese Geographical Science, 1997)